Ethylene-based resin composition and molded article

JP7660662B2Active Publication Date: 2025-04-11MITSUI CHEMICALS INC +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2023511467
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-03-04
Filing Date
2022-03-30
Publication Date
2025-04-11
Estimated Expiration
2042-03-30

AI Technical Summary

Technical Problem

There are problems such as neck-in phenomenon, molden film drop or vibration during the molding process, resulting in lowering of product yield and unstable shape.

Method used

The combination of ethylene-α-olefin copolymers containing specific melt characteristics and molecular structure is used to optimize the molding performance by adjusting its density, melt flow rate, melt tension and zero strain viscosity.

Benefits of technology

The excellent molding performance, mechanical strength, transparency and barrier properties of ethylene resin molded bodies are achieved, reducing the use of anti-blocking agents, and reducing costs and hygiene risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660662000001
    Figure 0007660662000001
  • Figure 0007660662000002
    Figure 0007660662000002
  • Figure 0007660662000003
    Figure 0007660662000003
Patent Text Reader

Abstract

[Problem] To provide an ethylene resin capable of producing by excellent moldability a molded body (especially a film) having excellent mechanical strength and an excellent balance of transparency and blocking resistance. [Solution] An ethylene resin composition (Z) including an ethylene-α-olefin copolymer (A) that satisfies requirements (1)-(4) and an ethylene-α-olefin copolymer (B) that satisfies requirements (a)-(c). (1) Density is 890-935 kg / m3 (2) MFR (190°C, 2.16 kg load) is 0.1 g / 10 min to less than 3.0 g / 10 min (3) MT (melt tension) / η* (shear viscosity) is 1.20×10-4 to 2.90×10-4 g / P (4) 0.01×10-13 × Mw3.4 ≤ η0 (zero shear viscosity) ≤ 3.5×10-13 × Mw3.4 (a) Density is 890-930 kg / m3 (b) MFR (190°C, 2.16 kg load) is 0.1-10 g / 10 min (c) 1.90×10-4 × Mw0.776 ≤ [η] ≤ 2.80×10-4 × Mw0.776
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ethylene-based resin composition, and a molded article, a film, and a multilayer film each containing the composition. [Background technology]

[0002] Ethylene-based polymers are used in various molding methods and applications, and various properties are required of ethylene-based polymers depending on the molding method and application. For example, in T-die molding, neck-in occurs, in which the film ends shrink toward the center. When neck-in occurs, the film width becomes smaller and the film ends become thicker than the center of the film. Therefore, if the neck-in is large, problems such as a decrease in product yield and failure to produce a product of the desired width occur. In blow molding, problems such as sagging and breakage of the molten film may occur, and in inflation molding, problems such as shaking and breakage of the molten film may occur. In order to suppress these problems, it is necessary to select an ethylene-based polymer with a high melt tension relative to its molecular weight.

[0003] Ethylene polymers without long chain branches obtained using metallocene catalysts have excellent mechanical strength, but have problems with moldability. For example, necking becomes large in T-die molding, sagging of the molten film occurs in blown molding, and wrinkling of the film occurs due to shaking of the molten film in inflation molding. High-pressure low-density polyethylene has high melt tension and is excellent in moldability, but because it has complex long chain branches, it is inferior in mechanical strength such as tensile strength, tear strength, and impact strength.

[0004] In order to solve such problems, various ethylene polymers into which long chain branches have been introduced have been disclosed. Patent Document 1 proposes a composition of an ethylene polymer obtained using a metallocene catalyst and high-pressure low-density polyethylene. However, when the content of high-pressure low-density polyethylene is high, it is expected that the mechanical strength such as tensile strength, tear strength and impact strength will be poor, and when the content of high-pressure low-density polyethylene is low, the improvement in melt tension is insufficient, so that it is expected that the moldability will be deteriorated, such as a large neck-in.

[0005] Patent Document 2 discloses an ethylene polymer obtained by solution polymerization in the presence of a catalyst consisting of ethylenebis(indenyl)hafnium dichloride and methylalumoxane, Patent Document 3 discloses an ethylene polymer obtained by gas phase polymerization in the presence of a catalyst consisting of ethylenebis(indenyl)zirconium dichloride and methylalumoxane supported on silica, Patent Document 4 discloses an ethylene polymer obtained by solution polymerization in the presence of a constrained geometry catalyst, and Patent Document 5 discloses an ethylene polymer obtained by gas phase polymerization in the presence of a catalyst consisting of racemic and meso isomers of Me2Si(2-Me-Ind)2 and methylalumoxane supported on silica. It is described that these ethylene polymers have improved melt tension and excellent moldability compared to linear ethylene polymers without long chain branches, but the neck-in is still large, so the improvement in moldability is insufficient, and it is expected that the improvement in the blocking resistance of the film is also insufficient. When an ethylene polymer is used for a film, an antiblocking agent is generally added to prevent blocking, but the addition of a large amount of an antiblocking agent is not preferred in some applications from the viewpoint of cost increase and hygienic properties of the contents, and therefore a film having excellent blocking resistance without using an antiblocking agent is desired.

[0006] Patent documents 6, 7, 8 and 9 disclose ethylene polymers and ethylene resin compositions in which the intrinsic viscosity and the weight average molecular weight satisfy a specific relationship, the melt tension and the shear viscosity satisfy a specific relationship, or the zero shear viscosity and the weight average molecular weight show a specific relationship. These ethylene polymers have improved take-off surging, and have improved neck-in and inflation moldability in T-die molding compared to conventional ethylene polymers in which long chain branches are introduced using a metallocene catalyst. However, further improvements in mechanical strength and transparency are desired. Although a film with high external haze due to minute irregularities on the film surface has excellent blocking resistance, a film with an excellent balance between transparency and blocking resistance is desired from the viewpoint of visibility of contents and defect inspection in the film. In addition, when the ethylene polymer is used in a bottle or the like, improvement in transparency is also desired. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 7-26079 [Patent Document 2] Japanese Patent Application Publication No. 2-276807 [Patent Document 3] Japanese Patent Application Publication No. 4-213309 [Patent Document 4] International Publication No. 93 / 08221 [Patent Document 5] Japanese Patent Application Publication No. 8-311260 [Patent Document 6] JP 2006-233207 A [Patent Document 7] JP 2009-197225 A [Patent Document 8] International Publication No. 2013 / 099927 [Patent Document 9] JP 2014-177506 A Summary of the Invention [Problem to be solved by the invention]

[0008] In view of such conventional techniques, a first object of the present invention is to provide an ethylene resin composition capable of producing a molded article (e.g., a film and a multilayer film having the film; the same applies below) having excellent moldability and mechanical strength compared to conventionally known ethylene resins, and a molded article obtained from the ethylene resin composition. A second object of the present invention is to provide an ethylene resin composition capable of producing a molded article which has excellent moldability, excellent mechanical strength, and an excellent balance between transparency and blocking resistance, as compared with conventionally known ethylene resins, and to provide a molded article obtained from the ethylene resin composition. A third object of the present invention is to provide an ethylene resin composition which has particularly excellent moldability and can produce a molded article having excellent mechanical strength as compared with conventionally known ethylene resins, and a molded article obtained from the ethylene resin composition. [Means for solving the problem]

[0009] As a result of intensive research, the present inventors have found that a composition containing two types of ethylene polymers having specific melting properties and molecular structures can solve the first problem, that is, it can produce a molded product (e.g., a film and a multilayer film having the film) having excellent moldability (i.e., excellent molten film stability in inflation molding, small neck-in in T-die molding, and no take-up surging) and excellent mechanical strength, and have thus completed the present invention.

[0010] The present invention for solving the first problem relates to, for example, the following [1]. [1] An ethylene-α-olefin copolymer (A) which is a copolymer of ethylene and an α-olefin having 4 to 10 carbon atoms and satisfies the following requirements (1) to (4); and (B) an ethylene-α-olefin copolymer which is a copolymer of ethylene and an α-olefin having 4 to 10 carbon atoms and satisfies the following requirements (a) to (c): Ethylene-based resin composition (Z). (1) Density is 890 kg / m 3 More than 935kg / m 3 It is in the following range: (2) The melt flow rate (MFR) under a load of 2.16 kg at 190°C is in the range of 0.1 g / 10 min or more and less than 3.0 g / 10 min. (3) Melt tension at 190°C [MT(g)] and shear viscosity at 200°C and angular velocity of 1.0 rad / sec [η * (P)] and the ratio [MT / η * (g / P) is 1.20×10 -4 More than 2.90 x 10 -4 It is in the following range: (4) The zero shear viscosity [η0(P)] at 200°C and the weight average molecular weight (Mw) measured by the GPC-viscosity detector method (GPC-VISCO) satisfy the following relationship (Eq-1). 0.01×10 -13 ×Mw 3.4 ≦η0≦3.5×10 -13 ×Mw 3.4 (Eq-1) (a) Density is 890 kg / m 3 More than 930kg / m 3 It is in the following range: (b) The melt flow rate (MFR) under a load of 2.16 kg at 190°C is in the range of 0.1 g / 10 min to 10 g / 10 min. (c) The intrinsic viscosity [[η] (dl / g)] measured in decalin at 135°C and the weight average molecular weight (Mw) measured by the GPC-viscosity detector method (GPC-VISCO) satisfy the following relational equation (Eq-4). 1.90×10 -4 ×Mw 0.776 ≦[η]≦ 2.80×10 -4 ×Mw 0.776 (Eq-4) The present inventors have also found that, among the ethylene-based resin compositions (Z) of [1] above, a composition containing the above two types of ethylene-based polymers in a specific ratio can solve the second problem, that is, a molded article having excellent moldability, excellent mechanical strength, and an excellent balance between transparency and blocking resistance can be produced. The present invention for solving the second problem relates to, for example, the following [2].

[0011] [2] The mass fraction (W A ) is 1% by mass or more and 50% by mass or less, and the mass fraction (W B ) is 50% by mass or more and 99% by mass or less (however, W A and W B The total of these is 100 mass %.) The ethylene resin composition (Z) of [1]. Furthermore, the present inventors have found that, among the ethylene-based resin compositions (Z) of [1] above, a composition containing the above two types of ethylene-based polymers in a specific ratio can solve the third problem, that is, a molded article having particularly excellent moldability and excellent mechanical strength can be produced. The present invention for solving the third problem relates, for example, to the following [3].

[0012] [3] The mass fraction (W A ) is more than 50 mass% and not more than 99 mass%, and the mass fraction (W B ) is 1 mass% or more and less than 50 mass% (however, W A and W B The total of these is 100 mass %.) The ethylene resin composition (Z) of [1]. The present invention further relates to, for example, the following [4] to

[12] .

[0013] [4] The ethylene resin composition (Z) according to any one of the above [1] to [3], wherein the ethylene-α-olefin copolymer (A) satisfies the following requirement (5): (5) The number average molecular weight (Mn), weight average molecular weight (Mw) and Z average molecular weight (Mz) measured by a GPC-viscosity detector method (GPC-VISCO) satisfy the following relational formula (Eq-2). -7.0 ≦ Mz / Mw - Mw / Mn ≦ 2.0 (Eq-2)

[0014] [5] The ethylene resin composition (Z) according to any one of the above [1] to [4], wherein the ethylene-α-olefin copolymer (A) further satisfies the following requirement (6): (6) The ratio Mz / Mw of the Z-average molecular weight (Mz) to the weight-average molecular weight (Mw) measured by the GPC-viscosity detector method (GPC-VISCO) is in the range of 4.0 or more and 15.0 or less.

[0015] [6] The ethylene resin composition (Z) according to any one of the above [1] to [5], wherein the ethylene-α-olefin copolymer (A) further satisfies the following requirement (7): (7) The intrinsic viscosity [[η] (dl / g)] measured in decalin at 135°C and the weight average molecular weight (Mw) measured by the GPC-viscosity detector method (GPC-VISCO) satisfy the following relational equation (Eq-3). 0.7×10 -4 ×Mw 0.776 ≦[η]≦ 1.65×10 -4 ×Mw 0.776 (Eq-3)

[0016] [7] The ethylene resin composition (Z) according to any one of [1] to [6] above, wherein the ethylene-α-olefin copolymer (A) satisfies the following requirement (8): (8) 1 The total of vinyl, vinylidene, di-substituted internal olefin, and tri-substituted internal olefin per 1000 carbon atoms (units / 1000C) measured by H-NMR is in the range of 0.1 to 1.0.

[0017] [8] The ethylene resin composition (Z) according to any one of [1] to [7] above, wherein the ethylene-α-olefin copolymer (A) satisfies the following requirement (9): (9) The melting curve obtained by differential scanning calorimetry (DSC) has multiple peaks.

[0018] [9] The ethylene-based resin composition (Z) according to any one of the above [1] to [8], further comprising a thermoplastic resin (excluding the above ethylene-α-olefin copolymer (A) and ethylene-α-olefin copolymer (B)).

[0019]

[10] A molded article comprising the ethylene resin composition (Z) according to any one of [1] to [9] above.

[0020]

[11] A film comprising the ethylene resin composition (Z) according to any one of [1] to [9] above.

[0021]

[12] A multilayer film comprising a layer made of the ethylene resin composition (Z) of any one of [1] to [9] above. Effect of the Invention

[0022] According to the ethylene-based resin composition (Z) of the present invention, a molded article (particularly a film) having excellent mechanical strength can be suitably produced due to its excellent moldability. Moreover, the ethylene-based resin composition (Z) according to the present invention [2] can be suitably produced into a molded article (particularly, a film) having excellent moldability, excellent mechanical strength, and an excellent balance between transparency and blocking resistance. Furthermore, the ethylene resin composition (Z) according to the present invention [3] has particularly excellent moldability and can be suitably used to produce molded articles (particularly films) having excellent mechanical strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The ethylene-based resin composition (Z) according to the present invention will be specifically described below together with the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B) which are its constituent components.

[0024] [Ethylene-based resin composition (Z)] [Ethylene-α-olefin copolymer (A)] The ethylene-α-olefin copolymer (A) is a copolymer of ethylene and an α-olefin having 4 to 10 carbon atoms, preferably an α-olefin having 6 to 10 carbon atoms. Examples of the α-olefin having 4 to 10 carbon atoms used for copolymerization with ethylene include 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, and 1-decene.

[0025] The ethylene-α-olefin copolymer (A) has the following properties (1) to (4). (1) Density is 890 kg / m 3 More than 935kg / m 3 Less than 900 kg / m 3 More than 925kg / m 3 Less than or equal to 905 kg / m 3 More than 922kg / m 3 It is in the following range:

[0026] When the density is equal to or higher than the lower limit, the surface of a film formed from the ethylene-based resin composition (Z) is less sticky, and when the density is equal to or lower than the upper limit, the impact strength of a film formed from the ethylene-based resin composition (Z) is good, and mechanical strengths such as heat seal strength and bag-breaking strength of a bag made from the film are good.

[0027] The density depends on the α-olefin content of the ethylene-α-olefin copolymer, and the lower the α-olefin content, the higher the density, and the higher the α-olefin content, the lower the density. The α-olefin content of the ethylene-α-olefin copolymer is determined by the composition ratio of α-olefin to ethylene (α-olefin / ethylene) in the polymerization system (for example, Walter Kaminsky, Makromol.Chem. 193, p.606(1992)), so that an ethylene-α-olefin copolymer having a density in the above range can be produced by increasing or decreasing the α-olefin / ethylene.

[0028] The density is measured as follows. The strand obtained when measuring MFR is heat treated at 100°C for 30 minutes and then allowed to stand at room temperature for 1 hour, after which it is measured by the density gradient tube method.

[0029] (2) The melt flow rate (MFR) is in the range of 0.1 g / 10 min or more and less than 3.0 g / 10 min, preferably 0.3 g / 10 min or more and 2.5 g / 10 min or less, and more preferably 0.5 g / 10 min or more and 2.0 g / 10 min or less.

[0030] When the melt flow rate (MFR) is equal to or higher than the lower limit, the shear viscosity of the ethylene-based resin composition (Z) is not too high and the extrusion load is good.When the melt flow rate (MFR) is equal to or lower than the upper limit, the mechanical strength of the ethylene-based resin composition (Z) is good.

[0031] The melt flow rate (MFR) is strongly dependent on the molecular weight; the smaller the MFR, the higher the molecular weight, and the higher the MFR, the lower the molecular weight. It is also known that the molecular weight of an ethylene-based polymer is determined by the composition ratio of hydrogen to ethylene (hydrogen / ethylene) in the polymerization system (for example, Kazuo Soga et al., Catalytic Olefin Polymerization, Kodansha Scientific, 1990, p. 376). Therefore, it is possible to increase or decrease the melt flow rate (MFR) of an ethylene-based polymer by increasing or decreasing the hydrogen / ethylene ratio. The melt flow rate (MFR) is measured according to JIS K 7210 under the conditions of 190°C and a load of 2.16 kg.

[0032] (3) Melt tension [MT(g)] and shear viscosity [η * (P) (P is Poise) and the ratio [MT / η * (g / P) is 1.20×10 -4 ~2.90×10 -4 , preferably 1.30 x 10 -4 ~2.70×10 -4 , more preferably 1.30×10 -4 ~2.45×10 -4 is in the range.

[0033] MT / η * When MT / η is equal to or higher than the lower limit, the ethylene-α-olefin copolymer (A) has a high melt tension relative to its molecular weight, and the ethylene-based resin composition (Z) has excellent moldability. * When is equal to or less than the upper limit, the ethylene resin composition (Z) has excellent mechanical strength.

[0034] MT / η * depends on the long chain branch content of the ethylene polymer, and the higher the long chain branch content, the lower the MT / η * The lower the long chain branch content, the greater the MT / η *Long chain branches are defined as branch structures with a length equal to or greater than the molecular weight (Me) between entanglement points contained in an ethylene polymer, and it is known that the introduction of long chain branches significantly changes the melt properties and moldability of ethylene polymers (for example, Kazuo Matsuura et al., eds., "Polyethylene Technology Reader," Kogyo Chosakai, 2001, pp. 32, 36). MT / η * can be adjusted by the type of component (A) or solid support (S) of the olefin polymerization catalyst (X) described below. Even when the same olefin polymerization catalyst (X) is used, it can be adjusted by the polymerization conditions or polymerization process. For example, by increasing the ethylene partial pressure, MT / η * The MT / η near the lower limit can be reduced by the manufacturing conditions of the manufacturing example 3 described later. * The MT / η * can be obtained.

[0035] The melt tension [MT(g)] is measured as follows. The melt tension (MT) (unit: g) is determined by measuring the stress when stretched at a constant speed. A capillary rheometer is used for the measurement (for example, in the examples described later, a capillary rheometer: Capillograph 1D manufactured by Toyo Seiki Seisakusho Co., Ltd. is used). The conditions are a resin temperature of 190°C, a melting time of 6 minutes, a barrel diameter of 9.55 mmφ, an extrusion speed of 15 mm / min, a winding speed of 24 m / min (if the molten filament breaks, the winding speed is reduced by 5 m / min), a nozzle diameter of 2.095 mmφ, and a nozzle length of 8 mm.

[0036] Shear viscosity at 200°C and angular velocity of 1.0 rad / sec [η * The shear viscosity (η * ) is the shear viscosity (η *The angular velocity [ω (rad / sec)] dispersion of the torque is measured in the range of 0.01≦ω≦100. A viscoelasticity measuring device is used for the measurement (for example, in the examples described later, a viscoelasticity measuring device Physica MCR301 manufactured by Anton Paar is used), a parallel plate with a diameter of 25 mm is used as a sample holder, and the sample thickness is about 2.0 mm. Five measurement points are set per ω digit. The amount of strain is appropriately selected in the range of 3 to 10% so that the torque can be detected within the measurement range and the torque is not exceeded.

[0037] The samples used for shear viscosity measurement were prepared using a molding machine (for example, a press molding machine manufactured by Shinto Metal Industries was used in the examples described later) under the following conditions: preheat temperature 190°C, preheat time 5 minutes, heating temperature 190°C, heating time 2 minutes, heating pressure 100 kgf / cm 2 , cooling temperature 20℃, cooling time 5 minutes, cooling pressure 100kgf / cm 2 A measurement sample is prepared by press molding to a thickness of 2 mm under the above conditions.

[0038] (4) The zero shear viscosity [η0(P)] at 200°C and the weight average molecular weight (Mw) measured by the GPC-viscosity detector method (GPC-VISCO) satisfy the following relationship (Eq-1). 0.01×10 -13 ×Mw 3.4 ≦η0≦3.5×10 -13 ×Mw 3.4 (Eq-1) Preferably, the following (Eq-1') is satisfied. 0.05×10 -13 ×Mw 3.4 ≦η0≦3.0×10 -13 ×Mw 3.4 (Eq-1') More preferably, the following (Eq-1") is satisfied. 0.1×10 -13 ×Mw 3.4 ≦η0≦2.5×10 -13 ×Mw 3.4 (Eq-1") When the zero shear viscosity [η0(P)] is plotted against the weight average molecular weight (Mw) in a double logarithmic scale, it is known that resins whose extensional viscosity does not show strain hardening, such as linear ethylene polymers without long chain branches, follow a power law with a slope of 3.4, whereas resins whose extensional viscosity shows strain rate hardening, such as high pressure low density polyethylene, show a zero shear viscosity [η0(P)] lower than the power law (C Gabriel, H.Munstedt, J.Rheol., 47(3), 619(2003)). When the zero shear viscosity [η0(P)] at 200°C is equal to or lower than the upper limit, the elongational viscosity of the ethylene polymer exhibits strain rate hardening, so that take-up surging does not occur. In addition, since the long chain branching is short and there are many molecules that connect crystalline lamellae of the same molecular weight, the ethylene resin composition (Z) has excellent mechanical strength (impact resistance).

[0039] In addition, when the molten resin flows into the die, extensional stress is generated by the extensional flow. When this extensional stress exceeds a critical value, brittle fracture occurs, and unstable flow occurs at the die exit, called melt fracture, and fine irregularities are formed on the surface of the molded product (FN Cogswell, Polymer Melt Rheology, Wiley, 1981). When the zero shear viscosity [η0(P)] is within the above range, the extensional stress becomes large at the strain rate in general molding processing, and melt fracture occurs moderately. Since this melt fracture forms fine irregularities on the film surface moderately, the film obtained from the ethylene-based resin composition (Z) has an excellent balance between transparency and blocking resistance.

[0040] The relationship between the zero shear viscosity [η0(P)] and the weight average molecular weight (Mw) is considered to depend on the content and length of long chain branches in the ethylene polymer. It is considered that the higher the content of long chain branches and the shorter the length of the long chain branches, the smaller the zero shear viscosity [η0(P)] will be, and the lower the content of long chain branches and the longer the length of the long chain branches, the larger the zero shear viscosity [η0(P)] will be.

[0041] The zero shear viscosity [η0(P)] can be adjusted by the type of component (A) or solid support (S) of the olefin polymerization catalyst (X) described later. Even when the same olefin polymerization catalyst (X) is used, the zero shear viscosity [η0(P)] can be adjusted by the polymerization conditions or polymerization process. For example, the zero shear viscosity [η0(P)] can be increased by increasing the ethylene partial pressure. The zero shear viscosity [η0(P)] near the lower limit can be obtained by the production conditions of Production Example 9 described later, and the zero shear viscosity [η0(P)] near the upper limit can be obtained by the production conditions of Production Example 6 described later.

[0042] The zero shear viscosity at 200°C [η0(P)] is measured as follows. At a measurement temperature of 200°C, shear viscosity (η * ) is measured in the range of 0.01≦ω≦100. A viscoelasticity measuring device is used for the measurement (for example, in the examples described later, a viscoelasticity measuring device Physica MCR301 manufactured by Anton Paar is used), a parallel plate with a diameter of 25 mm is used as a sample holder, and the sample thickness is about 2.0 mm. Five measurement points are set per ω digit. The amount of strain is appropriately selected in the range of 3 to 10% so that the torque can be detected within the measurement range and the torque is not exceeded.

[0043] The samples used for shear viscosity measurement were prepared using a molding machine (for example, a press molding machine manufactured by Shinto Metal Industries was used in the examples described later) under the following conditions: preheat temperature 190°C, preheat time 5 minutes, heating temperature 190°C, heating time 2 minutes, heating pressure 100 kgf / cm 2 , cooling temperature 20℃, cooling time 5 minutes, cooling pressure 100kgf / cm 2 A measurement sample is prepared by press molding to a thickness of 2 mm under the above conditions.

[0044] The zero shear viscosity (η0) is calculated by applying the Carreau model shown below to the actual rheology curve [shear viscosity (η * The angular velocity (ω) variance of the axial displacement is calculated by fitting the η * =η0〔1+(λω)a 〕 (n-1) / a (λ is a parameter with a time dimension, a is a fitting parameter, and n is the power law index of the material.)

[0045] The fitting by the nonlinear least squares method is performed so that d in the following equation is minimized.

[0046]

number

[0047] The weight average molecular weight (Mw) and the like are measured by gel permeation chromatography (GPC) as follows.

[0048] A differential refractometer and a capillary viscometer are used as detectors, the column temperature is 145°C, o-dichlorobenzene is used as mobile phase, the flow rate is 1.0 ml / min, the sample concentration is 0.1 wt%, and polystyrene is used as standard polymer. In the examples described below, an Agilent GPC-viscosity detector (GPC-VISCO) PL-GPC220 is used as a measuring device, two Agilent PLgel Olexis are used as analytical columns, and a Tosoh standard polystyrene is used. For molecular weight calculation, the actual viscosity is calculated from the viscometer and refractometer, and the number average molecular weight (Mn), weight average molecular weight (Mw), Z-average molecular weight (Mz), and molecular weight distribution (Mw / Mn, Mz / Mw) are obtained by actual universal calibration. The ethylene-α-olefin copolymer (A) preferably has the properties shown in the following (5).

[0049] (5) The number average molecular weight (Mn), weight average molecular weight (Mw) and Z average molecular weight (Mz) measured by a GPC-viscosity detector method (GPC-VISCO) satisfy the following relational formula (Eq-2). -7.0≦ Mz / Mw - Mw / Mn ≦2.0 (Eq-2) Preferably, the following relational formula (Eq-2') is satisfied. -6.0≦ Mz / Mw - Mw / Mn ≦1.0 (Eq-2') More preferably, the following relational formula (Eq-2") is satisfied. -5.0≦ Mz / Mw - Mw / Mn ≦0.0 (Eq-2") When Mz / Mw-Mw / Mn is large, the molecular weight distribution is broadened to the high molecular weight side. When Mz / Mw-Mw / Mn is equal to or higher than the lower limit, the ethylene-based resin composition (Z) has excellent melt film stability, and when it is equal to or lower than the upper limit, the ethylene-based resin composition (Z) has excellent thin film moldability.

[0050] Mz / Mw-Mw / Mn can be adjusted by the type of component (A) or solid support (S) of the olefin polymerization catalyst (X) described later, and can also be adjusted by the polymerization conditions or polymerization process even when the same olefin polymerization catalyst (X) is used. Mz / Mw-Mw / Mn near the lower limit can be obtained by the production conditions of Production Example 9 described later, and Mz / Mw-Mw / Mn near the upper limit can be obtained by the polymerization conditions of Production Example 10 described later. The number average molecular weight (Mn), weight average molecular weight (Mw) and Z average molecular weight (Mz) are measured by the methods described above. The ethylene-α-olefin copolymer (A) preferably has the properties shown in the following (6).

[0051] (6) The ratio (Mz / Mw) of Z-average molecular weight (Mz) to weight-average molecular weight (Mw) measured by a GPC-viscosity detector method (GPC-VISCO) is in the range of 4.0 to 15.0, preferably 5.0 to 12.0, and more preferably 6.0 to 10.0. The larger the Mz / Mw, the more high molecular weight components there are, and when Mz / Mw is equal to or higher than the lower limit, blocking resistance is excellent, and when Mz / Mw is equal to or lower than the upper limit, transparency is excellent.

[0052] Mz / Mw can be adjusted by the type of component (A) or solid support (S) of the olefin polymerization catalyst (X) described later, and can also be adjusted by the polymerization conditions or polymerization process even when the same olefin polymerization catalyst (X) is used. Mz / Mw near the lower limit can be obtained by the production conditions of Production Example 3 described later, and Mz / Mw near the upper limit can be obtained by the polymerization conditions of Production Example 10 described later. The ethylene-α-olefin copolymer (A) preferably has the properties shown in the following (7).

[0053] (7) The intrinsic viscosity [[η] (dl / g)] measured in decalin at 135°C and the weight average molecular weight (Mw) measured by the GPC-viscosity detector method (GPC-VISCO) satisfy the following relational equation (Eq-3). 0.7×10 -4 ×Mw 0.776 ≦[η]≦ 1.65×10 -4 ×Mw 0.776 (Eq-3) Preferably, the following (Eq-3') is satisfied. 0.7×10 -4 ×Mw 0.776 ≦[η]≦ 1.40×10 -4 ×Mw 0.776 (Eq-3') More preferably, the following (Eq-3") is satisfied. 0.8×10 -4 ×Mw 0.776 ≦[η]≦ 1.20×10 -4 ×Mw 0.776 (Eq-3")

[0054] It is known that when long chain branches are introduced into an ethylene polymer, the intrinsic viscosity [[η] (dl / g)] becomes smaller relative to the molecular weight compared to a linear ethylene polymer without long chain branches (for example, Walther Burchard, ADVANCES IN POLYMER SCIENCE, 143, Branched Polymer II, p. 137 (1999)). Therefore, the intrinsic viscosity [[η] (dl / g)] is 1.65×10 -4 ×Mw 0.776In the following cases, the ethylene polymer has many long chain branches and is excellent in moldability and flowability. The intrinsic viscosity [[η] (dl / g)] can be adjusted by the type of component (A) or solid support (S) of the olefin polymerization catalyst (X) described later. Even when the same olefin polymerization catalyst (X) is used, the intrinsic viscosity [[η] (dl / g)] can be adjusted by the polymerization conditions or polymerization process. For example, the intrinsic viscosity [[η] (dl / g)] can be increased by increasing the ethylene partial pressure. A limiting viscosity [[η] (dl / g)] near the lower limit can be obtained under the production conditions of Production Example 9 described later, and a limiting viscosity [[η] (dl / g)] near the upper limit can be obtained under the production conditions of Production Example 2 described later.

[0055] The intrinsic viscosity [[η] (dl / g)] is measured using decalin solvent as follows: Approximately 20 mg of the measurement sample is dissolved in 15 ml of decalin, and the specific viscosity ηsp is measured in an oil bath at 135°C. 5 ml of decalin solvent is added to this decalin solution to dilute it, and the specific viscosity ηsp is measured in the same manner. This dilution procedure is repeated two more times, and the value of ηsp / C when the concentration (C) is extrapolated to 0 as shown in the formula below is calculated as the intrinsic viscosity [η] (unit: dl / g). [η]=lim(ηsp / C) (C→0) The weight average molecular weight (Mw) is measured by the method described above. The ethylene-α-olefin copolymer (A) preferably has the properties shown in the following (8).

[0056] (8) 1 The numbers of vinyl, vinylidene, di-substituted internal olefin, and tri-substituted internal olefin measured by H-NMR satisfy the following relational formula (Eq-3). 0.1≦vinyl + vinylidene + disubstituted internal olefin + trisubstituted internal olefin≦1.0 (Eq-3) Preferably, the following relational formula (Eq-3') is satisfied. 0.3≦vinyl + vinylidene + disubstituted internal olefin + trisubstituted internal olefin≦0.9 (Eq-3') More preferably, the following relational formula (Eq-3") is satisfied. 0.5≦vinyl + vinylidene + disubstituted internal olefin + trisubstituted internal olefin≦0.8 (Eq-3")

[0057] The number of vinyls, vinylidenes, di-substituted internal olefins, and tri-substituted internal olefins in the polymer is 1 It is the number per 1000 carbon atoms contained in a polymer, measured by H-NMR. It is known that the production ratio and number of vinyl, vinylidene, disubstituted internal olefin, and trisubstituted internal olefin increase or decrease depending on the transition metal compound used (H.SAIKI, S.MAKOTO, T.MASAO, S.MORIHIKO, Y.AKIHIRO, J. Polym. Sci., A: Polym. Chem., 38, 4641 (2000)). These can be adjusted by the type of component (A) or solid support (S) of the olefin polymerization catalyst (X) described below. In addition, even when the same olefin polymerization catalyst (X) is used, it can be adjusted by the polymerization conditions or polymerization process, and for example, it can be increased or decreased by increasing or decreasing the ethylene partial pressure.

[0058] When the number of vinyl + vinylidene + di-substituted internal olefin + tri-substituted internal olefin is equal to or greater than the lower limit, long chain branching is easily generated and moldability is excellent. When the number of vinyl + vinylidene + di-substituted internal olefin + tri-substituted internal olefin is equal to or less than the upper limit, the molten film in the extrusion lamination is less susceptible to oxidation, and the heat sealability is excellent, and the transparency and mechanical strength of the molded product are excellent. 1 The numbers of vinyl, vinylidene, di-substituted internal olefins, and tri-substituted internal olefins measured by H-NMR (500 MHz) are measured using a nuclear magnetic resonance apparatus (for example, in the examples described later, a Bruker AVANCE III (Cryoprobe) nuclear magnetic resonance apparatus was used) as follows.

[0059] The measurement mode is single pulse, pulse width 45°. The number of points is 32k, the observation range is 20ppm (-6 to 14ppm), the repetition time is 7 seconds, and the number of integrations is 64. 20mg of sample is dissolved in 0.6ml of orthodichlorobenzene-D4, and then measured at 120℃. 1 The number of double bonds and total number of double bonds calculated from the signal integrals derived from various double bonds (vinyl, vinylidene, internal olefin) at 4.5 ppm to 5.8 ppm in the H-NMR spectrum. 1 The relative value of the total number of carbon atoms calculated from the total integrated value of the H signal is obtained, and the number of each type of double bond per 1000 carbon atoms of the polymer is calculated. The ethylene-α-olefin copolymer (A) preferably has the properties shown in the following (9).

[0060] (9) The melting curve obtained by differential scanning calorimetry (DSC) has multiple peaks. When there are multiple peaks, the content is low, indicating that the material has excellent heat sealability at low temperatures. Differential scanning calorimetry (DSC) is performed using a differential scanning calorimeter (for example, Diamond DSC manufactured by PerkinElmer was used in the examples described below) as follows. Approximately 5 mg of a sample is placed in an aluminum pan, heated to 200°C at 10°C / min, held at 200°C for 10 minutes, cooled to -30°C at 10°C / min, and then heated to 200°C at 10°C / min to obtain an endothermic curve. If this endothermic curve has two or more peaks, it means that there are multiple peaks in the melting curve obtained by differential scanning calorimetry (DSC).

[0061] [Ethylene-α-olefin copolymer (B)] The ethylene-α-olefin copolymer (B) is a copolymer of ethylene and an α-olefin having 4 to 10 carbon atoms, preferably an α-olefin having 6 to 10 carbon atoms. Examples of the α-olefin having 4 to 10 carbon atoms used for copolymerization with ethylene include 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, and 1-decene. The ethylene-α-olefin copolymer (B) has the following properties (a) to (c).

[0062] (a) Density is 890 kg / m 3 More than 930kg / m 3 Less than 900 kg / m 3 More than 925kg / m 3 Less than or equal to 905 kg / m 3 More than 920kg / m 3 It is in the following range:

[0063] When the density is equal to or higher than the lower limit, the surface of a film formed from the ethylene-based resin composition (Z) is less sticky, and when the density is equal to or lower than the upper limit, the impact strength of a film formed from the ethylene-based resin composition (Z) is good, and mechanical strengths such as heat seal strength and bag-breaking strength of a bag made from the film are good.

[0064] (b) The melt flow rate (MFR) is in the range of 0.1 g / 10 min or more and 10 g / 10 min or less, preferably 0.5 g / 10 min or more and 5.0 g / 10 min or less, and more preferably 0.8 g / 10 min or more and 3.0 g / 10 min or less.

[0065] When the melt flow rate (MFR) is equal to or higher than the lower limit, the film formed from the ethylene-based resin composition (Z) has few fish eyes and has a good appearance. When the melt flow rate (MFR) is equal to or lower than the upper limit, the ethylene-based resin composition (Z) has high melt tension and good moldability such as melt film stability.

[0066] (c) The intrinsic viscosity [[η] (dl / g)] measured in decalin at 135°C and the weight average molecular weight (Mw) measured by the GPC-viscosity detector method (GPC-VISCO) satisfy the following relational equation (Eq-4). 1.90×10 -4 ×Mw 0.776 ≦[η]≦ 2.80×10 -4 ×Mw 0.776 (Eq-4) Preferably, the following relational formula (Eq-4') is satisfied. 2.20×10 -4 ×Mw 0.776 ≦[η]≦ 2.60×10 -4 ×Mw 0.776 (Eq-4')

[0067] As described above, it is known that if an ethylene polymer does not have long chain branches, the intrinsic viscosity [[η] (dl / g)] is large relative to the molecular weight compared to an ethylene polymer having long chain branches. Therefore, an ethylene-α-olefin copolymer (B) having [[η] (dl / g)] equal to or greater than the lower limit is a linear ethylene-α-olefin copolymer substantially free of long chain branches. The ethylene resin composition (Z) of the present invention containing such an ethylene-α-olefin copolymer has high melt tension and excellent bubble stability.

[0068] <Ethylene-based resin composition (Z)> The ethylene-based resin composition (Z) according to the present invention contains the above ethylene-α-olefin copolymer (A) and the above ethylene-α-olefin copolymer (B). The mass fraction (W A ) and the mass fraction (W B ) is 100% by mass, A 1 to 50% by mass, W B When the content of the ethylene-based resin composition (Z) is 50 to 99 mass %, the ethylene-based resin composition (Z) has excellent moldability and mechanical strength, and a film formed from the ethylene-based resin composition (Z) has a particularly excellent balance between transparency and blocking resistance.

[0069] W A is more than 50% by mass and 99% by mass or less, W B When the content is 1 mass % or more and less than 50 mass %, the ethylene-based resin composition (Z) is excellent in moldability and mechanical strength, and in particular, can be molded at a lower resin pressure (or a higher melt tension).

[0070] W Ais preferably 5 to 40 mass %, more preferably 10 to 30 mass %. Within this range, the ethylene-based resin composition (Z) is excellent in moldability and mechanical strength, and a film formed from the ethylene-based resin composition (Z) is excellent in balance between transparency and blocking resistance.

[0071] The ethylene-based resin composition (Z) according to the present invention may be substantially composed of the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B), but is not limited thereto, and may contain, in addition to the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B), a thermoplastic resin other than the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B) (hereinafter referred to as "other thermoplastic resin"). The ethylene-based resin composition (Z) obtained as a thermoplastic resin composition by blending the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B) with the "other thermoplastic resin" has excellent moldability and mechanical strength.

[0072] The blend ratio of the sum of the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B) to the "other thermoplastic resin" (total mass of ethylene-α-olefin copolymer (A) and ethylene-α-olefin copolymer (B) / mass of other thermoplastic resin) is usually 99.9 / 0.1 to 0.1 / 99.9, preferably 90 / 10 to 10 / 90, and more preferably 70 / 30 to 30 / 70.

[0073] (Other thermoplastic resins) Other thermoplastic resins include crystalline thermoplastic resins such as polyolefins, polyamides, polyesters, and polyacetals; and non-crystalline thermoplastic resins such as polystyrene, acrylonitrile-butadiene-styrene copolymers (ABS), polycarbonates, polyphenylene oxides, and polyacrylates. Polyvinyl chloride is also preferably used.

[0074] Specific examples of the polyolefin include ethylene polymers, propylene polymers, butene polymers, 4-methyl-1-pentene polymers, 3-methyl-1-butene polymers, and hexene polymers. Among them, ethylene polymers, propylene polymers, and 4-methyl-1-pentene polymers are preferred, and in the case of ethylene polymers, they may be conventional ethylene polymers or ethylene-polar group-containing vinyl copolymers, but conventional ethylene polymers are more preferred. The ethylene polymers and propylene polymers may be ethylene polymers and propylene polymers containing biomass-derived monomers, respectively.

[0075] The ethylene-based resin composition (Z) of the present invention may contain additives such as weather resistance stabilizers, heat resistance stabilizers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, lubricants, pigments, dyes, nucleating agents, plasticizers, antioxidants, hydrochloric acid absorbers and antioxidants, as necessary, within the scope of not impairing the object of the present invention.

[0076] The total amount of additives is generally 10 parts by mass or less, preferably 1 part by mass or less, and more preferably 0.5 parts by mass or less, per 100 parts by mass of the total of the components other than the additives in the ethylene resin composition (Z).

[0077] <Method for producing ethylene-α-olefin copolymer> Next, the method for producing the ethylene-α-olefin copolymer (A) will be described. The ethylene-α-olefin copolymer (A) can be efficiently produced by polymerizing ethylene and an α-olefin having 4 to 10 carbon atoms in the presence of an olefin polymerization catalyst (X) consisting of the following components:

[0078] [Olefin polymerization catalyst (X)] The olefin polymerization catalyst (X) comprises the following component (A) and a solid support (S).

[0079] <Component (A)> Component (A) is a transition metal compound represented by the following formula (1) (hereinafter also referred to as "transition metal compound (1)"). Olefin polymerization catalyst (X) contains at least one transition metal compound (1). That is, as component (A), one or more transition metal compounds (1) may be used.

[0080] [ka]

[0081] In the above formula (1), M is a zirconium atom or a hafnium atom, and is preferably a zirconium atom. In the above formula (1), n ​​is an integer of 1 to 4, and preferably 2, selected so that the transition metal compound (1) is electrically neutral.

[0082] In the formula (1), each X is independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing group, an oxygen-containing group, a nitrogen-containing group, or a conjugated diene derivative group, and is preferably a halogen atom or a hydrocarbon group having 1 to 20 carbon atoms. The halogen atom includes fluorine, chlorine, bromine and iodine, and chlorine is particularly preferred.

[0083] Examples of the hydrocarbon group having 1 to 20 carbon atoms include linear or branched alkyl groups such as methyl, ethyl, 1-propyl, 1-butyl, 1-pentyl, 1-hexyl, 1-heptyl, 1-octyl, isopropyl, sec-butyl (butan-2-yl), tert-butyl (2-methylpropan-2-yl), isobutyl (2-methylpropyl), pentan-2-yl, 2-methylbutyl, isopentyl (3-methylbutyl), neopentyl (2,2-dimethylpropyl), cyamyl (1,2-dimethylpropyl), isohexyl (4-methylpentyl), 2,2-dimethylbutyl, 2,3-dimethylbutyl, 3,3-dimethylbutyl, thexyl (2,3-dimethylbut-2-yl), 4,4-dimethylpentyl; Vinyl group, allyl group, propenyl group (prop-1-en-1-yl group), iso-propenyl group (prop-1-en-2-yl group), allenyl group (prop-1,2-dien-1-yl group), but-3-en-1-yl group, crotyl group (but-2-en-1-yl group), but-3-en-2-yl group, methallyl group (2-methylallyl group), buta-1,3-dienyl group, pentaerythritol group, linear or branched alkenyl groups or unsaturated double bond-containing groups, such as ter-4-en-1-yl group, pent-3-en-1-yl group, pent-2-en-1-yl group, iso-pentenyl group (3-methylbut-3-en-1-yl group), 2-methylbut-3-en-1-yl group, pent-4-en-2-yl group, and prenyl group (3-methylbut-2-en-1-yl group); linear or branched alkynyl groups or unsaturated triple bond-containing groups such as ethynyl, prop-2-yn-1-yl, and propargyl (prop-1-yn-1-yl) groups; linear or branched alkyl groups containing aromatic groups and unsaturated double bond-containing groups, such as benzyl group, 2-methylbenzyl group, 4-methylbenzyl group, 2,4,6-trimethylbenzyl group, 3,5-dimethylbenzyl group, cuminyl group (4-isopropylbenzyl group), 2,4,6-tri-isopropylbenzyl group, 4-tert-butylbenzyl group, 3,5-di-tert-butylbenzyl group, 1-phenylethyl group, and benzhydryl group (diphenylmethyl group); cyclic saturated hydrocarbon groups such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cycloheptatrienyl group, a norbornyl group, a norbornenyl group, a 1-adamantyl group, and a 2-adamantyl group; Aromatic substituents such as phenyl, tolyl (methylphenyl), xylyl (dimethylphenyl), mesityl (2,4,6-trimethylphenyl), cumenyl (isopropylphenyl), julyl (2,3,5,6-tetramethylphenyl), 2,6-di-isopropylphenyl, 2,4,6-tri-isopropylphenyl, 4-tert-butylphenyl, 3,5-di-tert-butylphenyl, naphthyl, biphenyl, tert-phenyl, binaphthyl, acenaphthalenyl, phenanthryl, anthracenyl, pyrenyl, and ferrocenyl. Of these, preferred are a methyl group, an iso-butyl group, a neopentyl group, a cyamyl group, a benzyl group, a phenyl group, a tolyl group, a xylyl group, a mesityl group, and a cumenyl group.

[0084] The hydrocarbon group having 1 to 20 carbon atoms may be a halogen-substituted hydrocarbon group in which some or all of the hydrogen atoms of the hydrocarbon group having 1 to 20 carbon atoms have been substituted with halogen atoms, and examples thereof include a fluoromethyl group, a trifluoromethyl group, a trichloromethyl group, a 2,2,2-trifluoroethyl group, a pentafluoroethyl group, a pentachloroethyl group, a pentafluorophenylmethyl group, a fluorophenyl group, a difluorophenyl group, a trifluorophenyl group, a tetrafluorophenyl group, a pentafluorophenyl group, a trifluoromethylphenyl group, and a bistrifluoromethylphenyl group, with a pentafluorophenyl group being preferred.

[0085] Examples of the silicon-containing group include a trimethylsilyl group, a triethylsilyl group, a tri-iso-propylsilyl group, a diphenylmethylsilyl group, a tert-butyldimethylsilyl group, a tert-butyldiphenylsilyl group, a triphenylsilyl group, a tris(trimethylsilyl)silyl group, and a trimethylsilylmethyl group, and preferably a trimethylsilylmethyl group.

[0086] Examples of the oxygen-containing group include a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an allyloxy group, an n-butoxy group, a sec-butoxy group, an isobutoxy group, a tert-butoxy group, a benzyloxy group, a methoxymethoxy group, a phenoxy group, a 2,6-dimethylphenoxy group, a 2,6-di-isopropylphenoxy group, a 2,6-di-tert-butylphenoxy group, a 2,4,6-trimethylphenoxy group, a 2,4,6-tri-isopropylphenoxy group, an acetoxy group, a pivaloyloxy group, a benzoyloxy group, a trifluoroacetoxy group, a perchlorate anion, and a periodate anion, and preferably a methoxy group, an ethoxy group, an isopropoxy group, or a tert-butoxy group.

[0087] Examples of the nitrogen-containing group include an amino group, a cyano group, a methylamino group, a dimethylamino group, an ethylamino group, a diethylamino group, an allylamino group, a diallylamino group, a benzylamino group, a dibenzylamino group, a pyrrolidinyl group, a piperidinyl group, a morpholyl group, a pyrrolyl group, and a bistriflyl imide group.

[0088] Examples of the conjugated diene derivative group include a 1,3-butadienyl group, an isoprenyl group (2-methyl-1,3-butadienyl group), a piperylenyl group (1,3-pentadienyl group), a 2,4-hexadienyl group, a 1,4-diphenyl-1,3-pentadienyl group, and a cyclopentadienyl group, and preferably a 1,3-butadienyl group or a 1,3-pentadienyl group.

[0089] In the above formula (1), Q is a carbon atom or a silicon atom, and is preferably a silicon atom. In the formula (1), R 1 ~R 14 each independently represents a hydrogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing group having 1 to 20 carbon atoms, an oxygen-containing group having 1 to 20 carbon atoms, or a nitrogen-containing group having 1 to 20 carbon atoms, and is preferably a hydrogen atom, a hydrocarbon group having 1 to 20 carbon atoms, or an oxygen-containing group having 1 to 20 carbon atoms.

[0090] R 1 ~R 14 Examples of the hydrocarbon group having 1 to 20 carbon atoms as the alkyl group include linear or branched alkyl groups such as a methyl group, an ethyl group, a 1-propyl group, a 1-butyl group, a 1-pentyl group, a 1-hexyl group, a 1-heptyl group, a 1-octyl group, an isopropyl group, a sec-butyl group (butan-2-yl group), a tert-butyl group (2-methylpropan-2-yl group), an isobutyl group (2-methylpropyl group), a pentan-2-yl group, a 2-methylbutyl group, an isopentyl group (3-methylbutyl group), a neopentyl group (2,2-dimethylpropyl group), a cyamyl group (1,2-dimethylpropyl group), an isohexyl group (4-methylpentyl group), a 2,2-dimethylbutyl group, a 2,3-dimethylbutyl group, a 3,3-dimethylbutyl group, a thexyl group (2,3-dimethylbut-2-yl group), and a 4,4-dimethylpentyl group; Vinyl group, allyl group, propenyl group (prop-1-en-1-yl group), iso-propenyl group (prop-1-en-2-yl group), allenyl group (prop-1,2-dien-1-yl group), but-3-en-1-yl group, crotyl group (but-2-en-1-yl group), but-3-en-2-yl group, methallyl group (2-methylallyl group), buta-1,3-dienyl group, pentaerythritol group, linear or branched alkenyl groups or unsaturated double bond-containing groups, such as ter-4-en-1-yl group, pent-3-en-1-yl group, pent-2-en-1-yl group, iso-pentenyl group (3-methylbut-3-en-1-yl group), 2-methylbut-3-en-1-yl group, pent-4-en-2-yl group, and prenyl group (3-methylbut-2-en-1-yl group); linear or branched alkynyl groups or unsaturated triple bond-containing groups such as ethynyl, prop-2-yn-1-yl, and propargyl (prop-1-yn-1-yl) groups; linear or branched alkyl groups containing aromatic groups and unsaturated double bond-containing groups, such as benzyl group, 2-methylbenzyl group, 4-methylbenzyl group, 2,4,6-trimethylbenzyl group, 3,5-dimethylbenzyl group, cuminyl group (4-isopropylbenzyl group), 2,4,6-tri-isopropylbenzyl group, 4-tert-butylbenzyl group, 3,5-di-tert-butylbenzyl group, 1-phenylethyl group, benzhydryl group (diphenylmethyl group), and pentafluorophenylmethyl group; cyclic saturated hydrocarbon groups such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cycloheptatrienyl group, a norbornyl group, a norbornenyl group, a 1-adamantyl group, and a 2-adamantyl group; Aromatic substituents such as phenyl, tolyl (methylphenyl), xylyl (dimethylphenyl), mesityl (2,4,6-trimethylphenyl), cumenyl (isopropylphenyl), julyl (2,3,5,6-tetramethylphenyl), 2,6-di-isopropylphenyl, 2,4,6-tri-isopropylphenyl, 4-tert-butylphenyl, 3,5-di-tert-butylphenyl, naphthyl, biphenyl, tert-phenyl, binaphthyl, acenaphthalenyl, phenanthryl, anthracenyl, pyrenyl, and ferrocenyl; halogen-substituted hydrocarbon groups in which some or all of the hydrogen atoms of the aforementioned hydrocarbon groups having 1 to 20 carbon atoms have been substituted with halogen atoms, such as a fluoromethyl group, a trifluoromethyl group, a trichloromethyl group, a 2,2,2-trifluoroethyl group, a pentafluoroethyl group, a pentachloroethyl group, a pentafluorophenylmethyl group, a fluorophenyl group, a difluorophenyl group, a trifluorophenyl group, a tetrafluorophenyl group, a pentafluorophenyl group, a trifluoromethylphenyl group, and a bistrifluoromethylphenyl group; and preferably, a methyl group, an ethyl group, a 1-propyl group, a 1-butyl group, a 1-pentyl group, a 1-hexyl group, a 1-heptyl group, a 1-octyl group, an isopropyl group, a sec-butyl group, a tert-butyl group, an isobutyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, an allyl group, a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclooctenyl group, a norbornyl group, a bicyclo[2.2.2]octan-1-yl group, a 1-adamantyl group, a 2-adamantyl group, or a benzyl group. , benzhydryl, cumyl, 1,1-diphenylethyl, trityl, 2-phenylethyl, 3-phenylpropyl, cinnamyl, phenyl, tolyl, xylyl, mesityl, cumenyl, 2,6-di-isopropylphenyl, 2,4,6-tri-isopropylphenyl, 4-tert-butylphenyl, 3,5-di-tert-butylphenyl, 4-adamantylphenyl, naphthyl, biphenyl, tert-phenyl, binaphthyl, phenanthryl, anthracenyl, ferrocenyl, and pentafluorophenyl.

[0091] R 1 ~R 14 As the silicon-containing group having 1 to 20 carbon atoms as the aryl group, a trimethylsilyl group, a triethylsilyl group, a tri-iso-propylsilyl group, a tert-butyldimethylsilyl group, a triphenylsilyl group, a cyclopentadienyldimethylsilyl group, a cyclopentadienyldiphenylsilyl group, an indenyldimethylsilyl group, a fluorenyldimethylsilyl group, a 4-trimethylsilylphenyl group, a 4-triethylsilylphenyl group, a 4-tri-iso-propylsilylphenyl group, a 3,5-bis(trimethylsilyl)phenyl group, and the like are preferred, and examples thereof include a trimethylsilyl group, a triethylsilyl group, a tert-butyldimethylsilyl group, a 4-trimethylsilylphenyl group, a 4-triethylsilylphenyl group, a 4-tri-iso-propylsilylphenyl group, and a 3,5-bis(trimethylsilyl)phenyl group.

[0092] R 1 ~R14 Examples of the oxygen-containing group having 1 to 20 carbon atoms as the above include a methoxy group, an ethoxy group, an isopropoxy group, an allyloxy group, an n-butoxy group, a tert-butoxy group, a prenyloxy group, a benzyloxy group, a phenoxy group, a naphthoxy group, a toluyloxy group, an isopropylphenoxy group, an allylphenoxy group, a tert-butylphenoxy group, a methoxyphenoxy group, a biphenyloxy group, a binaphthyloxy group, an allyloxymethyl group, a benzyloxymethyl group, a phenoxymethyl group, a methoxyethyl group, a methoxyallyl group, a benzyloxyallyl group, a phenoxyallyl group, a dimethoxymethyl group, a dioxolanyl group, a tetramethyldioxolanyl group, a dioxanyl group, a dimethyldioxanyl group, a methoxyphenyl group, an isopropoxyphenyl group, an aryloxy group, an aryloxymethyl group, a aryloxymethyl group, a aryloxymethyl group, a aryloxyethyl group, a methoxyallyl group, a benzyloxyallyl group, a phenoxyallyl group, a dimethoxymethyl group, a dioxolanyl group, a tetramethyldioxolanyl group, a dioxanyl group, a dimethyldioxanyl group, a methoxyphenyl group, an isopropoxyphenyl group, an aryloxymethyl group, a ... Examples of such groups include an aloxyphenyl group, a phenoxyphenyl group, a methylenedioxyphenyl group, a 3,5-dimethyl-4-methoxyphenyl group, a 3,5-di-tert-butyl-4-methoxyphenyl group, a furyl group, a methylfuryl group, a tetrahydropyranyl group, a furyl group, a benzofuryl group, and a dibenzofuryl group, and preferred are a methoxy group, an isopropoxy group, a tert-butoxy group, an allyloxy group, a phenoxy group, a dimethoxymethyl group, a dioxolanyl group, a methoxyphenyl group, an isopropoxyphenyl group, an allyloxyphenyl group, a phenoxyphenyl group, a 3,5-dimethyl-4-methoxyphenyl group, a 3,5-di-tert-butyl-4-methoxyphenyl group, a furyl group, a methylfuryl group, a benzofuryl group, and a dibenzofuryl group.

[0093] R 1 ~R 14Examples of the nitrogen-containing group having 1 to 20 carbon atoms as the above-mentioned compound include an amino group, a dimethylamino group, a diethylamino group, an allylamino group, a benzylamino group, a dibenzylamino group, a pyrrolidinyl group, a piperidinyl group, a morpholyl group, a dimethylaminomethyl group, a benzylaminomethyl group, a pyrrolidinylmethyl group, a dimethylaminoethyl group, a pyrrolidinylethyl group, a dimethylaminopropyl group, a pyrrolidinylpropyl group, a dimethylaminoallyl group, a pyrrolidinylallyl group, an aminophenyl group, a dimethylaminophenyl group, a 3,5-dimethyl-4-dimethylaminophenyl group, a 3,5-di-iso-propyl-4-dimethylaminophenyl group, a julolidinyl group, a tetramethyljulolidinyl group, a pyrrolidinylphenyl group, a pyrrolylphenyl group, a carbazolylphenyl group, a di-tert-butylcarbazolylphenyl group, a Examples of such groups include a zolylphenyl group, a pyrrolyl group, a pyridyl group, a quinolyl group, a tetrahydroquinolyl group, an isoquinolyl group, a tetrahydro-iso-quinolyl group, an indolyl group, an indolinyl group, a carbazolyl group, a di-tert-butylcarbazolyl group, an imidazolyl group, a dimethylimidazolidinyl group, a benzimidazolyl group, an oxazolyl group, an oxazolidinyl group, and a benzoxazolyl group. Of these, preferred are an amino group, a dimethylamino group, a diethylamino group, a pyrrolidinyl group, a dimethylaminophenyl group, a 3,5-dimethyl-4-dimethylaminophenyl group, a 3,5-di-iso-propyl-4-dimethylaminophenyl group, a julolidinyl group, a tetramethyljulolidinyl group, a pyrrolidinylphenyl group, a pyrrolyl group, a pyridyl group, a carbazolyl group, and an imidazolyl group.

[0094] In the formula (1), R 1 ~R 6 Adjacent substituents (e.g., R 1 and R 2 , R 2 and R 3 , R 3 and R 4 , R 4 and R 5 , and R 5 and R 6) may be bonded to each other to form a ring which may have a substituent. In this case, the ring formed is preferably a 5- to 8-membered ring consisting of a saturated hydrocarbon (excluding the hydrocarbon of the indenyl ring portion) or an unsaturated hydrocarbon which may have a substituent and is condensed with the indenyl ring portion. When a plurality of rings are present, they may be the same or different. Although not particularly limited as long as the effects of the present invention are exhibited, the ring is more preferably a 5- or 6-membered ring, and in this case, examples of the structure formed by combining the ring with the indenyl ring portion of the mother nucleus include a benzoindenyl ring, a tetrahydroindacene ring, and a cyclopentatetrahydronaphthalene ring, and a benzoindenyl ring and a tetrahydroindacene ring are preferred. These rings may have a substituent.

[0095] In the formula (1), R 7 ~R 12 Adjacent substituents (e.g., R 7 and R 8 , R 8 and R 9 , R 9 and R 10 , R 10 and R 11 , and R 11 and R 12 ) may be bonded to each other to form a ring which may have a substituent. In this case, the ring formed is preferably a 5- to 8-membered ring consisting of a saturated hydrocarbon (excluding the hydrocarbon of the indenyl ring portion) or an unsaturated hydrocarbon which may have a substituent and is condensed with the indenyl ring portion. When a plurality of rings are present, they may be the same or different. Although not particularly limited as long as the effects of the present invention are exhibited, the ring is more preferably a 5- or 6-membered ring. In this case, examples of the structure formed by combining the ring with the indenyl ring portion of the mother nucleus include a benzoindenyl ring, a tetrahydroindacene ring, a cyclopentatetrahydronaphthalene ring, a tetrahydrofluorene ring, and a fluorene ring, and a benzoindenyl ring and a tetrahydroindacene ring are preferred. These rings may have a substituent.

[0096] In the formula (1), R13 and R 14 may be bonded to each other to form a ring containing Q, and these rings may have a substituent. In this case, the ring formed is preferably a 3- to 8-membered saturated or unsaturated ring which may have a substituent. There is no particular limitation as long as the effect of the present invention is exhibited, but it is preferably a 4- to 6-membered ring. In this case, examples of the structure combined with Q include a cyclobutane ring, a cyclopentane ring, a fluorene ring, a silacyclobutane (siletan) ring, a silacyclopentane (silorane) ring, a silacyclohexane (silinane) ring, and a silafluorene ring, and a cyclopentane ring, a silacyclobutane ring, and a silacyclopentane ring are preferred. These rings may have a substituent.

[0097] Specific examples of the transition metal compound (1) are shown below, but the scope of the present invention is not particularly limited thereto. For convenience, the ligand structure excluding the portion represented by MXn (metal portion) of the transition metal compound (1) is represented by the 2-indenyl ring portion, the 1-indenyl ring portion, the indenyl ring portion R 1 , R 6 and R 8 Substituent, indenyl ring moiety R 2 , R 5 , R 9 and R 12 Substituent, indenyl ring moiety R 3 , R 4 , R 10 and R 11 Substituent, 1-indenyl ring moiety R 7 The structure of the substituent and the bridge part is divided into seven parts. The abbreviation for the 2-indenyl ring part is α, the abbreviation for the 1-indenyl ring part is β, and the abbreviation for the indenyl ring part R 1 , R 6 and R 8 The abbreviation for the substituent is γ, and the indenyl ring portion is R 2 , R 5 , R 9 and R 12 The abbreviation of the substituent is δ, and the indenyl ring portion is R 3 , R 4 , R 10 and R 11 The abbreviation of the substituent is ε, and the 1-indenyl ring portion R7 The abbreviation for the substituent is ζ, the abbreviation for the structure of the crosslinked portion is η, and the abbreviations for each substituent are shown in [Table 1] to [Table 7].

[0098] [Table 1]

[0099] [Table 2]

[0100] In addition, the wavy lines in the above [Tables 1] and [Table 2] indicate the bonding sites with the crosslinked moieties.

[0101] [Table 3]

[0102] R in Table 3 1 , R 6 and R 8 The substituents in any combination may be the same or different from one another.

[0103] [Table 4]

[0104] R in Table 4 2 , R 5 , R 9 and R 12 The substituents in any combination may be the same or different from one another.

[0105] [Table 5]

[0106] R in Table 5 3 , R 4 , R 10 and R 11The substituents in any combination may be the same or different from one another.

[0107] [Table 6]

[0108] [Table 7]

[0109] Specific examples of the metal moiety MXn include: ZrF2, ZrCl2, ZrBr2, ZrI2, Zr(Me)2, Zr(Bn)2, Zr(Allyl)2, Zr(CH2-tBu)2, Zr(1,3-butadienyl), Zr(1,3-pentadienyl), Zr(2,4-hexadienyl), Zr(1,4-diphenyl-1,3-pentadienyl), Zr(CH2-Si(Me)3)2, Zr(ОMe)2, Zr(ОiPr)2, Zr(NMe2)2, Zr(ОMs)2, Zr(ОTs)2, Zr(ОTf)2, HfF2, HfCl2, HfBr2, HfI2, Hf(Me)2, Hf(Bn)2, Hf(Allyl)2, Hf(CH2-tBu)2, Hf(1,3-butadienyl), Hf(1,3-pentadienyl), Hf(2,4-hexadienyl), Hf(1,4-diphenyl-1,3-pentadienyl), Hf(CH2-Si(Me)3)2, Hf(ОMe)2, Hf(ОiPr)2, Hf(NMe2)2, Hf(ОMs)2, Hf(ОTs)2, Hf(ОTf)2 Me is a methyl group, Bn is a benzyl group, tBu is a tert-butyl group, Si(Me)3 is a trimethylsilyl group, OMe is a methoxy group, OMiPr is an iso-propoxy group, NMe2 is a dimethylamino group, OMs is a methanesulfonate group, OTs is a p-toluenesulfonate group, and OTf is a trifluoromethanesulfonate group.

[0110] According to the above notation, the 2-indenyl ring portion is α-1 in [Table 1], the 1-indenyl ring portion is β-5 in [Table 2], and the indenyl ring portion R 1, R 6 and R 8 The substituents are all γ-1,2-indenyl ring moiety R in [Table 3] 2 and R 5 The substituents are all δ-1,2-indenyl ring moiety R in [Table 4] 3 and R 4 The substituents are all ε-1,1-indenyl ring moiety R in [Table 5]. 7 The substituent is ζ-30, 1-indenyl ring moiety R in [Table 6] 9 The substituent is δ-38 in [Table 4], 1-indenyl ring moiety R 12 In the case where the substituent is δ-3 in [Table 4], the bridging portion is η-20 in [Table 7], and the metal portion MXn is ZrCl2, the compound represented by the following formula [6] is exemplified.

[0111] [ka]

[0112] In addition, the 2-indenyl ring portion is α-1 in [Table 1], the 1-indenyl ring portion is β-2 in [Table 2], and the indenyl ring portion R 1 , R 6 and R 8 The substituents are all γ-1,2-indenyl ring moiety R in [Table 3] 2 and R 5 The substituents are all δ-2,2-indenyl ring moiety R in [Table 4] 3 and R 4 The substituents are all ε-1,1-indenyl ring moiety R in [Table 5]. 7 In the case where the substituent is ζ-1 in [Table 6], the bridging portion is η-4 in [Table 7], and the metal portion MXn is Zr(NMe2)2, the compound represented by the following formula [7] is exemplified.

[0113] [ka]

[0114] In addition, the 2-indenyl ring portion is α-3 in [Table 1], the 1-indenyl ring portion is β-1 in [Table 2], and the 2-indenyl ring portion R 1 and R 6 The substituents are all γ-2 in [Table 3], the indenyl ring portion R 2 , R 5 and R 12 The substituents are all δ-1, 1-indenyl ring moiety R in [Table 4] 7 The substituent is the ζ-12, 1-indenyl ring moiety R in [Table 6] 8 The substituent is the γ-1,1-indenyl ring moiety R in [Table 3] 9 The substituent is δ-42 in [Table 4], 1-indenyl ring moiety R 10 The substituent is the ε-3,1-indenyl ring moiety R in [Table 5]. 11 In the case where the substituent is ε-12 in [Table 5], the bridging portion is η-31 in [Table 7], and the metal portion MXn is HfMe2, the compound represented by the following formula [8] is exemplified.

[0115] [ka]

[0116] In addition, the 2-indenyl ring portion is α-1 in [Table 1], the 1-indenyl ring portion is β-1 in [Table 2], and the 2-indenyl ring portion R 1 and R 6 The substituents are all γ-1,2-indenyl ring moiety R in [Table 3] 2 The substituent is δ-7, 2-indenyl ring moiety R in [Table 4] 3 , R 4 , R 10 and R 11 The substituents are all the ε-1,2-indenyl ring moiety R in [Table 5]. 5 The substituent is the δ-2,1-indenyl ring moiety R in [Table 4] 7 The substituent is the ζ-1, 1-indenyl ring moiety R in [Table 6] 8 The substituent is the γ-9,1-indenyl ring moiety R in [Table 3] 9 and R 12In the case where the substituents are all composed of a combination of δ-1 in [Table 4] and the bridging portion is composed of a combination of η-29 in [Table 7], and the metal portion MXn is Zr (1,3-pentadienyl), the compound represented by the following formula [9] is exemplified.

[0117] [ka]

[0118] The transition metal compound (1) can be produced by utilizing a conventionally known method, and the production method is not particularly limited. The starting material, the substituted indene compound, can be produced by a known method, and the production method is not particularly limited. Known production methods include, for example, those described in "Organometallics 1994, 13, 954.", "Organometallics 2006, 25, 1217.", JP2006-509059A, "Bioorg.Med.Chem. 2008, 16, 7399.", WO2009 / 080216A, "Organometallics 2011, 30, 5744.", JP2011-500800A, "Organometallics 2012, 31, 4962.", and "Chem.Eur.J. 2012,18,4174.", JP 2012-012307 A, JP 2012-121882 A, JP 2014-196319 A, JP 2014-513735 A, JP 2015-063495 A, JP 2016-501952 A, JP 2019-059933 A, and the like.

[0119] Known methods for producing the transition metal compound (1) and the precursor compound (ligand) are described in, for example, Macromolecules 2001, 34, 2072, Macromolecules 2003, 36, 9325, Organometallics 2004, 23, 5332, Eur. J. Inorg. Chem. 2005, 1003, Eur. J. Inorg. Chem. 2009, 1759, and the like.

[0120] In addition, the transition metal compound (1) has two faces (front and back) of the indenyl ring portion that is bonded to the central metal via the bridge portion. Therefore, when the 2-indenyl ring portion does not have a symmetrical plane, there are two structural isomers, as shown by the following general formula [10a] or [10b].

[0121] [ka]

[0122] Similarly, the substituent R of the bridging portion 13 and R 14 are not identical, there exist two structural isomers, as shown in the following general formula [11a] or [11b].

[0123] [ka]

[0124] Purification and separation of these structural isomer mixtures, or selective production of structural isomers, can be performed by known methods, and the production method is not particularly limited. Known production methods include those described as the production method of the transition metal compound (1) above, as well as production methods disclosed in JP-A-10-109996, "Organometallics 1999,18,5347," "Organometallics 2012,31,4340," and JP-T-2011-502192.

[0125] Within the scope of the transition metal compound (1), the transition metal compound may be used alone or in combination of two or more kinds, or a structural isomer mixture may be used, or a structural isomer may be used alone or in combination of two or more kinds. As described above, according to the present invention, an ethylene-based polymer having many long chain branches introduced therein can be produced with high catalytic activity by using only the transition metal compound (1) as a transition metal compound constituting an olefin polymerization catalyst, but one or more transition metal compounds other than the transition metal compound (1) may be used in combination as the transition metal compound within the scope of not impairing this effect. In this case, the transition metal compound (1) may be in any of the above-mentioned forms.

[0126] <Solid Carrier (S)> The solid support (S) contained in the olefin polymerization catalyst (X) is an inorganic compound or an organic compound, and is a granular or fine particle solid. Examples of the inorganic compound used as the solid support (S) include porous oxides, solid aluminoxane compounds, inorganic chlorides, clays, clay minerals, and ion-exchangeable layered compounds.

[0127] The porous oxides include SiO2, Al2O3, MgO, ZrO, TiO2, B2O3, CaO, ZnO, BaO, ThO2, etc., or composites or mixtures containing these, specifically natural or synthetic zeolites, SiO2-MgO, SiO2-Al2O3, SiO2-TiO2, SiO2-V2O5, SiO2-Cr2O3, SiO2-TiO2-MgO, etc. Among these, those containing SiO2 as the main component are preferred.

[0128] In addition, the above-mentioned porous oxide may contain small amounts of carbonates, sulfates, nitrates, and oxide components such as Na2CO3, K2CO3, CaCO3, MgCO3, Na2SO4, Al2(SO4)3, BaSO4, KNO3, Mg(NO3)2, Al(NO3)3, Na2O, K2O, and Li2O.

[0129] The properties of such porous oxides vary depending on the type and production method, but as a solid support (S), the particle size is usually 0.2 to 300 μm, preferably 1 to 200 μm, and the specific surface area is usually 50 to 1200 m. 2 / g, preferably 100 to 1000m 2 / g, and the pore volume is usually 0.3-30 cm 3 / g range is preferable. Such a support is calcined, for example, at 100 to 1000°C, preferably 150 to 700°C, as required, before use.

[0130] Examples of the solid aluminoxane compound include an aluminoxane having a structure represented by the following general formula (Sa), an aluminoxane having a structure represented by the following general formula (Sb), and an aluminoxane having a structure including a repeating unit represented by the following general formula (Sc) and a repeating unit represented by the following general formula (Sd).

[0131] [ka]

[0132] In the above formulas (Sa) to (Sd), R e are each independently a hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 4 carbon atoms, and specific examples thereof include hydrocarbon groups such as methyl, ethyl, propyl, isopropyl, isopropenyl, n-butyl, sec-butyl, tert-butyl, pentyl, hexyl, octyl, decyl, dodecyl, tridecyl, tetradecyl, hexadecyl, octadecyl, eicosyl, cyclohexyl, cyclooctyl, phenyl, tolyl, and ethylphenyl groups, with methyl, ethyl, and isobutyl groups being preferred, and methyl being particularly preferred. e A part of is replaced by halogen atoms such as chlorine and bromine, and the halogen content is R e In the above formulae (Sc) and (Sd), a straight line not connected to an atom on one side represents a bond to another atom not shown.

[0133] In the formulae (Sa) and (Sb), r represents an integer of 2 to 500, preferably 6 to 300, and particularly preferably 10 to 100. In the formulae (Sc) and (Sd), s and t each represent an integer of 1 or more. r, s, and t are selected so that the aluminoxane can be substantially maintained in a solid state in the reaction environment in which it is used.

[0134] The solid aluminoxane compound is different from conventionally known olefin polymerization catalyst supports, and does not contain inorganic solid components such as silica or alumina, or organic polymer components such as polyethylene or polystyrene, but is solidified with an alkylaluminum compound as the main component. The term "solid" means that the aluminoxane component maintains a substantially solid state in the reaction environment in which it is used. More specifically, the aluminoxane component maintains a substantially solid state when the component (A) is brought into contact with the aluminoxane component to prepare an olefin polymerization catalyst (e.g., an ethylene polymerization catalyst) as described below, and when the prepared olefin polymerization catalyst is used to polymerize an olefin (e.g., ethylene) (e.g., suspension polymerization).

[0135] The easiest method to check whether the aluminoxane component is in a solid state is to check visually, but in many cases, for example, during polymerization, visual confirmation is difficult. In that case, it can be judged, for example, from the properties of the polymer powder obtained after polymerization and the state of adhesion to the reactor. Conversely, if the properties of the polymer powder are good and adhesion to the reactor is small, even if a part of the aluminoxane component is eluted to some extent under the polymerization environment, it does not deviate from the gist of the present invention. Examples of indices for judging the properties of the polymer powder include bulk density, particle shape, surface shape, and the degree of presence of amorphous polymers, but from the viewpoint of quantitativeness, polymer bulk density is preferred. The bulk density is usually within the range of 0.01 to 0.9, preferably 0.05 to 0.6, and more preferably 0.1 to 0.5.

[0136] The solubility of the solid aluminoxane compound in n-hexane maintained at 25° C. is usually in the range of 0 to 40 mol %, preferably 0 to 20 mol %, and particularly preferably 0 to 10 mol %.

[0137] The dissolution ratio is determined by adding 2 g of the solid aluminoxane compound carrier to 50 ml of n-hexane kept at 25° C., stirring for 2 hours, separating the solution using a G-4 glass filter, and measuring the aluminum concentration in the filtrate. Therefore, the dissolution ratio is determined as the ratio of aluminum atoms present in the filtrate to the amount of aluminum atoms equivalent to 2 g of the aluminoxane used.

[0138] As the solid aluminoxane compound, known solid aluminoxanes can be used without limitation, and for example, the solid polyaluminoxane composition described in International Publication No. 2014 / 123212 can be used. Known production methods include, for example, those described in JP-B-7-42301, JP-A-6-220126, JP-A-6-220128, JP-A-11-140113, JP-A-11-310607, JP-A-2000-38410, JP-A-2000-95810, and International Publication No. 2010 / 55652.

[0139] The average particle diameter of the solid aluminoxane compound is generally in the range of 0.01 to 50,000 μm, preferably 0.1 to 1,000 μm, and particularly preferably 1 to 200 μm. The average particle diameter of the solid aluminoxane compound is obtained by observing the particles with a scanning electron microscope, measuring the particle diameters of 100 or more particles, and averaging the particle diameters by weight. First, the particle diameter d of each particle is measured by sandwiching the particle image between two parallel lines in the horizontal and vertical directions, and is obtained by the following formula. Particle size d = ((horizontal length) 2 +(Vertical length) 2 ) 0.5

[0140] Next, the weight average particle diameter of the solid aluminoxane compound is calculated from the particle diameter d and the number of particles n obtained above according to the following formula. Average particle diameter=Σnd 4 / Σnd 3

[0141] The solid aluminoxane compound has a specific surface area of ​​50 to 1000 m 2 / g, preferably 100 to 800m 2 / g and the pore volume is 0.1-2.5 cm 3 / g is preferable.

[0142] Examples of the inorganic halide include MgCl2, MgBr2, MnCl2, and MnBr2. The inorganic halide may be used as it is, or may be used after being pulverized by a ball mill or a vibration mill. In addition, the inorganic halide may be dissolved in a solvent such as alcohol, and then precipitated into fine particles by a precipitating agent.

[0143] Clay is usually composed mainly of clay minerals. An ion-exchangeable layered compound is a compound having a crystal structure in which the planes formed by ionic bonds or the like are stacked in parallel with weak bonding forces, and the ions contained therein are exchangeable. Most clay minerals are ion-exchangeable layered compounds. These clays, clay minerals, and ion-exchangeable layered compounds are not limited to natural products, and artificially synthesized products can also be used.

[0144] Examples of clays, clay minerals, or ion-exchangeable layered compounds include clays, clay minerals, and ionic crystalline compounds having layered crystal structures such as hexagonal close packing type, antimony type, CdCl2 type, and CdI2 type.

[0145] Examples of such clays and clay minerals include kaolin, bentonite, kibushi clay, gairome clay, allophane, hisingerite, pyrophyllite, ummo group, montmorillonite group, vermiculite, ryokudeite group, palygorskite, kaolinite, nacrite, dickite, halloysite, and the like. Examples of ion-exchangeable layered compounds include crystalline acid salts of polyvalent metals such as α-Zr(HAsO4)2·H2O, α-Zr(HPO4)2, α-Zr(KPO4)2·3H2O, α-Ti(HPO4)2, α-Ti(HAsO4)2·H2O, α-Sn(HPO4)2·H2O, γ-Zr(HPO4)2, γ-Ti(HPO4)2, γ-Ti(NH4PO4)2·H2O, and the like.

[0146] Such clays, clay minerals, or ion-exchangeable layered compounds preferably have a pore volume of 0.1 cc / g or more, particularly preferably 0.3 to 5 cc / g, of pores with a radius of 20 Å or more as measured by mercury intrusion porosimetry. 4 When a support having a pore volume of less than 0.1 cc / g with a radius of 20 Å or more is used, it tends to be difficult to obtain high polymerization activity.

[0147] It is also preferable to subject the clay and clay minerals to chemical treatment. As the chemical treatment, any of surface treatments that remove impurities adhering to the surface and treatments that affect the crystalline structure of the clay can be used. Specific examples of chemical treatments include acid treatment, alkali treatment, salt treatment, and organic treatment. In addition to removing impurities from the surface, acid treatment increases the surface area by dissolving cations such as Al, Fe, and Mg in the crystalline structure. In alkali treatment, the crystalline structure of the clay is destroyed, resulting in a change in the structure of the clay. In addition, salt treatment and organic treatment form ion complexes, molecular complexes, organic derivatives, etc., which can change the surface area and interlayer distance.

[0148] The ion-exchangeable layered compound may be a layered compound in which the space between layers is expanded by utilizing the ion exchangeability and exchanging the exchangeable ions between layers with other large bulky ions. Such bulky ions play a role of supporting the layered structure and are usually called pillars. The introduction of another substance between layers of a layered compound in this way is called intercalation. Examples of guest compounds to be intercalated include cationic inorganic compounds such as TiCl4 and ZrCl4, metal alkoxides such as Ti(OR)4, Zr(OR)4, PO(OR)3, and B(OR)3 (R is a hydrocarbon group, etc.), [Al 13 O4(OH) 24 ] 7+ , [Zr4(OH) 14 ] 2+ , [Fe3O(OCOCH3)6] + Metal hydroxide ions such as these can be used. These compounds can be used alone or in combination of two or more. When these compounds are intercalated, polymers obtained by hydrolysis of metal alkoxides (R is a hydrocarbon group, etc.) such as Si(OR)4, Al(OR)3, Ge(OR)4, etc., and colloidal inorganic compounds such as SiO2 can also be coexisted. Examples of pillars include oxides produced by intercalating the above metal hydroxide ions between layers and then dehydrating them with heat.

[0149] The clay, clay mineral, and ion-exchangeable layered compound may be used as is, or after treatment such as ball milling or sieving. They may also be used after adding and adsorbing new water or after heat dehydration treatment. Furthermore, they may be used alone or in combination of two or more.

[0150] Examples of the organic compound used as the solid carrier (S) include granular or particulate solids having a particle size in the range of 10 to 300 μm. Specific examples of the organic compound include polymers mainly composed of olefins having 2 to 14 carbon atoms such as ethylene, propylene, 1-butene, and 4-methyl-1-pentene, polymers or reaction products mainly composed of vinylcyclohexane, styrene, and divinylbenzene, and granular or particulate solids composed of modified products thereof. From the viewpoint of preventing foreign substances during molding, the solid carrier (S) is preferably a porous oxide.

[0151] <Component (C)> The olefin polymerization catalyst (X) may preferably further contain a component (C). The component (C) is at least one compound selected from the group consisting of an organometallic compound (c-1) represented by the following general formulas (3) to (5), an organoaluminum oxy compound (c-2), and a compound (c-3) that reacts with the component (A) to form an ion pair.

[0152] R a m Al(OR b ) n H p X q ···(3) In formula (3), R a and R b each independently represent a hydrocarbon group having 1 to 15 carbon atoms, X represents a halogen atom, m is a number where 0 < m ≦ 3, n is a number where 0 ≦ n < 3, p is a number where 0 ≦ p < 3, q is a number where 0 ≦ q < 3, and m + n + p + q = 3.

[0153] M a AlR a 4···(4) In formula (4), M a represents Li, Na, or K, and R a represents a hydrocarbon group having 1 or more and 15 or less carbon atoms.

[0154] R a rM b R b s X t (5) In formula (5), R a and R b each independently represents a hydrocarbon group having 1 to 15 carbon atoms; M b is selected from Mg, Zn and Cd, X represents a halogen atom, and r is 0. <r≦2、sは0≦s≦1、tは0≦t≦1であり、かつr+s+t=2である。

[0155] Among the organometallic compounds (c-1), those represented by the formula (3) are preferred, specifically, trialkylaluminum such as trimethylaluminum, triethylaluminum, triisopropylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, and tri-2-ethylhexylaluminum; Dialkylaluminum halides such as dimethylaluminum chloride, diethylaluminum chloride, diisopropylaluminum chloride, diisobutylaluminum chloride, and dimethylaluminum bromide; Alkyl aluminum sesquihalides such as methyl aluminum sesquichloride, ethyl aluminum sesquichloride, isopropyl aluminum sesquichloride, butyl aluminum sesquichloride, and ethyl aluminum sesquibromide; Alkyl aluminum dihalides such as methyl aluminum dichloride, ethyl aluminum dichloride, isopropyl aluminum dichloride, ethyl aluminum dibromide, etc.; alkylaluminum hydrides such as dimethylaluminum hydride, diethylaluminum hydride, dihydrophenylaluminum hydride, diisopropylaluminum hydride, di-n-butylaluminum hydride, diisobutylaluminum hydride, diisohexylaluminum hydride, diphenylaluminum hydride, dicyclohexylaluminum hydride, di-sec-heptylaluminum hydride, and di-sec-nonylaluminum hydride; Dialkylaluminum alkoxides such as dimethylaluminum ethoxide, diethylaluminum ethoxide, diisopropylaluminum methoxide, and diisobutylaluminum ethoxide etc.

[0156] An example of the formula (4) is lithium aluminum hydride, and an example of the formula (5) is a dialkylzinc compound described in JP-A-2003-171412, which can also be used in combination with a phenol compound.

[0157] The organoaluminum oxy compound (c-2) is preferably an organoaluminum oxy compound prepared from trialkylaluminum or tricycloalkylaluminum, and particularly preferably an aluminoxane prepared from trimethylaluminum or triisobutylaluminum, such as methylaluminoxane. Such organoaluminum oxy compounds can be used alone or in combination of two or more.

[0158] Examples of the compound (c-3) that reacts with the component (A) to form an ion pair include Lewis acids, ionic compounds, borane compounds, and carborane compounds, as well as heteropoly compounds and isopoly compounds, as described in, for example, JP-T-1-501950, JP-T-1-502036, JP-A-3-179005, JP-A-3-179006, JP-A-3-207703, JP-A-3-207704, and US Pat. No. 5,321,106.

[0159] In the olefin polymerization catalyst (X), when an organoaluminum oxy compound such as methylaluminoxane is used in combination as a cocatalyst component, not only does the catalyst exhibit extremely high polymerization activity for olefin compounds, but it also makes it possible to easily prepare a solid support component containing the cocatalyst component by reacting with active hydrogen in the solid support. For this reason, it is preferable that component (C) contains at least an organoaluminum oxy compound (c-2).

[0160] <How to use each ingredient and the order of addition> The olefin polymerization catalyst (X) can be prepared by mixing and contacting the components (A) and (S), and optionally the component (C), in an inert hydrocarbon.

[0161] Regarding the method of contacting each component, when paying attention to the order of contact, for example, (i) A method of contacting component (S) with component (A) (ii) A method in which component (S) is contacted with component (C) and then with component (A). (iii) A method in which component (A) is contacted with component (C) and then with component (S). (iv) A method of contacting component (S) with component (C) and then contacting a mixture of component (A) and component (C), (v) A method of contacting component (S) with component (C), further contacting with component (C), and then contacting with a mixture of component (A) and component (C). When a plurality of components (C) are used, the components (C) may be the same or different. Among the above methods, (i), (ii) and (iii) are preferred.

[0162] In each method showing the above contact order form, in the step including contact of component (S) with component (C) and the step including contact of component (S) with component (A), fouling during the polymerization reaction is suppressed and the particle properties of the resulting polymer are improved by making component (G) coexist. As component (G), a compound having a polar functional group can be used, and a nonionic surfactant is preferable, and a polyalkylene oxide block, a higher aliphatic amide, a polyalkylene oxide, a polyalkylene oxide alkyl ether, an alkyl diethanolamine, a polyoxyalkylene alkylamine, a glycerin fatty acid ester, and an N-acyl amino acid are more preferable. These may be used alone or in combination of two or more kinds.

[0163] The solvent used in the preparation of the olefin polymerization catalyst (X) includes inert hydrocarbon solvents, and specific examples thereof include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane; and mixtures thereof.

[0164] In the contact between component (C) and component (S), the reactive site in component (C) reacts with the reactive site in component (S) to chemically bond, forming a contact product between component (C) and component (S). The contact time between component (C) and component (S) is usually 1 minute to 20 hours, preferably 30 minutes to 10 hours, and the contact temperature is usually -50 to 200°C, preferably -20 to 120°C. If the initial contact between component (C) and component (S) is performed suddenly, component (S) will collapse due to the heat generated by the reaction or the reaction energy, and the morphology of the resulting solid catalyst component will deteriorate, and when this is used in polymerization, continuous operation will often be difficult due to poor polymer morphology. Therefore, in the initial contact between component (C) and component (S), it is preferable to contact them at a lower temperature in order to suppress the heat generated by the reaction, or to control the heat generated by the reaction and react at a rate that can maintain the initial contact temperature. The same applies when component (C) is contacted with component (S) and then component (C) is contacted. The contact weight ratio of component (C) to component (S) (weight of component (C) / weight of component (S)) can be selected arbitrarily. However, a higher contact weight ratio allows a larger amount of component (A) to be contacted, thereby improving the catalytic activity per weight of the solid catalyst component.

[0165] The contact weight ratio of component (C) to component (S) [=weight of component (C) / weight of component (S)] is preferably 0.05 to 3.0, particularly preferably 0.1 to 2.0. When the contact product of component (C) and component (S) is contacted with component (A), the contact time is usually 1 minute to 20 hours, and preferably 1 minute to 10 hours, and the contact temperature is usually within the range of -50 to 200°C, and preferably -50 to 100°C.

[0166] Component (C-1) is used in an amount such that the molar ratio [(C-1) / M] of component (C-1) to the total transition metal atoms (M) in component (A) is usually 0.01 to 100,000, preferably 0.05 to 50,000.

[0167] Component (C-2) is used in an amount such that the molar ratio [(C-2) / M] of component (C-2) (calculated as aluminum atoms) to the total transition metal atoms (M) in component (A) is usually 10 to 500,000, and preferably 20 to 100,000.

[0168] Component (C-3) is used in an amount such that the molar ratio of component (C-3) to the total transition metal atoms (M) in component (A) [(C-3) / M] is usually 1-10, preferably 1-5.

[0169] The ratio of component (C) to the total transition metal atoms (M) in component (A) can be determined by inductively coupled plasma emission spectrometry (ICP analysis). For ethylene polymerization, the olefin polymerization catalyst (X) can be used as is, but it can also be used after prepolymerizing an olefin with this olefin polymerization catalyst to form a prepolymerization catalyst (XP).

[0170] The prepolymerization catalyst (XP) can be prepared by prepolymerizing ethylene or the like in the presence of the olefin polymerization catalyst (X), usually in an inert hydrocarbon solvent, and can be carried out in any of a batchwise, semi-continuous, and continuous manner, and can be carried out under reduced pressure, normal pressure, or increased pressure. Furthermore, it is desirable to produce the prepolymerization catalyst (XP) in an amount of 0.01 to 1000 g, preferably 0.1 to 800 g, and more preferably 0.2 to 500 g, per 1 g of the solid catalyst component by the prepolymerization.

[0171] The prepolymerized catalyst (XP) produced in the inert hydrocarbon solvent may be separated from the suspension and then suspended again in the inert hydrocarbon, and ethylene may be introduced into the resulting suspension. Alternatively, ethylene may be introduced into the suspension after drying.

[0172] The prepolymerization temperature is −20 to 80° C., preferably 0 to 60° C., and the prepolymerization time is about 0.5 to 100 hours, preferably 1 to 50 hours. For the prepolymerization, an olefin containing ethylene as a main component is preferably used.

[0173] The form of the solid catalyst component used in the prepolymerization can be any of those already mentioned without any restrictions. If necessary, component (C) is used, and the organometallic compound (c-1) represented by the above formula (3) is preferably used. When component (C) is used, component (C) is used in an amount such that the molar ratio (Al / M) of aluminum atom (Al) in component (C) to transition metal atom (M) in component (A) is 0.1 to 10,000, preferably 0.5 to 5,000.

[0174] The concentration of the olefin polymerization catalyst (X) in the prepolymerization system is usually 1 to 1000 g / L, preferably 10 to 500 g / L, in terms of the volume ratio of the olefin polymerization catalyst / polymerization. During the prepolymerization, the above-mentioned component (G) may be allowed to coexist for the purpose of suppressing fouling or improving particle properties.

[0175] Furthermore, for the purpose of improving the fluidity of the prepolymerized catalyst (XP) and suppressing the occurrence of heat spots, sheeting, and polymer lumps during polymerization, the prepolymerized catalyst (XP) once produced by prepolymerization may be brought into contact with the component (G).

[0176] The temperature when the component (G) is contacted is usually from −50 to 50° C., and preferably from −20 to 50° C., and the contact time is usually from 1 minute to 20 hours, and preferably from 5 minutes to 10 hours. When the olefin polymerization catalyst (X) is contacted with the component (G), the component (G) is used in an amount of 0.1 to 20 parts by weight, preferably 0.3 to 10 parts by weight, and more preferably 0.4 to 5 parts by weight, per 100 parts by weight of the olefin polymerization catalyst (X).

[0177] The mixing and contacting of the olefin polymerization catalyst (X) and the component (G) can be carried out in an inert hydrocarbon solvent, and examples of the inert hydrocarbon solvent include those similar to those mentioned above. In the method for producing an ethylene polymer according to the present invention, a prepolymerized catalyst (XP) that has been dried (hereinafter also referred to as a "dried prepolymerized catalyst") can be used as the olefin polymerization catalyst (X). Drying of the prepolymerized catalyst (XP) is usually carried out after removing the hydrocarbon, which is the dispersion medium, from the obtained suspension of the prepolymerized catalyst by filtration or the like.

[0178] The prepolymerized catalyst (XP) is dried by maintaining the prepolymerized catalyst (XP) at a temperature of 70°C or less, preferably in the range of 20 to 50°C, under a flow of inert gas. The amount of volatile components in the obtained dried prepolymerized catalyst is desirably 2.0% by weight or less, preferably 1.0% by weight or less. The amount of volatile components in the dried prepolymerized catalyst is preferably as small as possible, and there is no particular lower limit, but in practice it is 0.001% by weight. The drying time is usually 1 to 48 hours, depending on the drying temperature.

[0179] The dry prepolymerized catalyst has excellent fluidity and can be stably supplied to a polymerization reactor. Furthermore, when the dry prepolymerized catalyst is used, the solvent used for suspension does not need to be entrained in the gas phase polymerization system, and therefore the polymerization can be stably carried out.

[0180] [Method of producing ethylene polymer] Next, the method for producing an ethylene-based polymer according to the present invention will be described. An ethylene-based polymer is obtained by polymerizing (homopolymerizing or copolymerizing) ethylene in the presence of the above-mentioned olefin polymerization catalyst (X). By using the olefin polymerization catalyst (X), it is possible to efficiently produce a low-density ethylene-based copolymer having many long-chain branches, which has high polymerization activity, excellent moldability and mechanical strength. The ethylene-based polymer of the present invention refers to a polymer containing 10 mol % or more of ethylene.

[0181] In the present invention, the polymerization can be carried out by any of liquid phase polymerization methods such as solution polymerization and suspension polymerization, or gas phase polymerization methods. In the suspension polymerization method and gas phase polymerization method, it is preferable to use the above-mentioned prepolymerized catalyst (XP).

[0182] Specific examples of the inert hydrocarbon medium used in the liquid phase polymerization method include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, kerosene, etc., alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc., aromatic hydrocarbons such as benzene, toluene, xylene, etc., halogenated hydrocarbons such as ethylene chloride, chlorobenzene, dichloromethane, etc., and mixtures thereof. In the liquid phase polymerization method, the olefin itself can also be used as the solvent.

[0183] When ethylene is polymerized using the above-mentioned olefin polymerization catalyst, the component (A) is usually added in an amount of 1×10 -12 ~1×10 -1 Molar, preferably 1 x 10 -8 ~1×10 -2 In addition, component (C) is used, and in particular, the organoaluminum compound represented by formula (3) in (c-1) is preferably used.

[0184] The polymerization temperature of ethylene using the prepolymerization catalyst (XP) is usually in the range of −50 to +200° C., preferably 0 to 170° C., and particularly preferably 60 to 170° C. The polymerization pressure is usually in the range of normal pressure to 100 kgf / cm.2 , preferably normal pressure to 50kgf / cm 2 The polymerization reaction can be carried out in any of batch, semi-continuous and continuous modes. The polymerization can also be carried out in two or more stages with different reaction conditions.

[0185] The molecular weight of the resulting polymer can be adjusted by adding hydrogen to the polymerization system or by changing the polymerization temperature. Generally, the more low molecular weight components there are, the more they adhere to the walls of the polymerization reactor and the agitator blades, which can lead to a decrease in productivity due to the burden on the cleaning process. Component (G) can be added during polymerization to suppress fouling or improve particle properties.

[0186] In the present invention, the monomer supplied together with ethylene to the copolymerization reaction is one or more monomers selected from α-olefins having 4 to 10 carbon atoms, preferably α-olefins having 6 to 10 carbon atoms. Specific examples of α-olefins having 4 to 10 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, and 1-decene. In addition, monomers other than ethylene and α-olefins having 4 to 10 carbon atoms may or may not be supplied within a range that does not impair the effects of the present invention.

[0187] <Method for producing ethylene-α-olefin copolymer (B)> The ethylene-α-olefin copolymer (B) can be obtained by polymerizing ethylene and an α-olefin having 4 to 10 carbon atoms, and the polymerization catalyst and polymerization conditions used are not particularly limited as long as the above-mentioned requirements are satisfied. As the ethylene-α-olefin copolymer (B), for example, a commercially available product such as linear low-density polyethylene, ethylene-α-olefin copolymer, or high-density polyethylene can be used. When using a commercially available product, for example, a product satisfying the requirements (a) to (c) may be selected from LLDPE EVOLUE (registered trademark) and ULTSEX (registered trademark) manufactured by Prime Polymer Co., Ltd.

[0188] <Production method of ethylene-based resin composition (Z)> The ethylene-based resin composition (Z) can be produced by melt-kneading the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B), or by dry-blending pellets of the ethylene-α-olefin copolymer (A) and pellets of the ethylene-α-olefin copolymer (B). When produced by melt-kneading, a continuous extruder or an internal kneader can be used. For example, a single-screw extruder, a twin-screw extruder, a mixing roll, a Banbury mixer, a kneader, and the like can be mentioned. Among these, it is preferable to use a single-screw extruder and / or a twin-screw extruder from the viewpoints of economy, processing efficiency, and the like.

[0189] When the melt kneading and dry blending are carried out, in addition to the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B), the "other thermoplastic resin" may be blended. In addition to the "other thermoplastic resin", or instead of the "other thermoplastic resin", the "additive" may be further blended.

[0190] The order of adding the "other thermoplastic resin" and the "additive" is not particularly limited. For example, the "other thermoplastic resin" and the "additive" may be blended simultaneously with one or both of the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B), or may be added after kneading the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B).

[0191] The ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B) may each contain a constitutional unit derived from at least one type of biomass-derived ethylene or α-olefin. The same type of monomer constituting the polymer may be only biomass-derived monomers, may be only fossil fuel-derived monomers, or may contain both biomass-derived monomers and fossil fuel-derived monomers. The biomass-derived monomer is a monomer obtained from any renewable natural raw material and its residue, such as a plant-derived or animal-derived monomer, including fungi, yeast, algae, and bacteria, and has a carbon-based isotope of 1×10 C. -12 The biomass-derived ethylene and α-olefin are obtained, for example, by a conventionally known method. It is preferable from the viewpoint of reducing the environmental load that the ethylene-α-olefin copolymer (A) and / or the ethylene-α-olefin copolymer (B) contain a structural unit derived from a biomass-derived monomer.

[0192] [Molded body, film, multilayer film] By processing the ethylene-based resin composition (Z) according to the present invention, a molded product, preferably a film or a multilayer film, having excellent moldability, excellent mechanical strength such as impact strength, high transparency, and excellent rigidity can be obtained. Here, this multilayer film has at least one layer made of the ethylene-based resin composition (Z), and preferably, in this multilayer film, at least one surface layer is made of the ethylene-based resin composition (Z). The substrate constituting this multilayer film may be made of the ethylene-based resin composition (Z) or may be made of a material other than the ethylene-based resin composition (Z).

[0193] The ethylene-based resin composition (Z) of the present invention is processed by general film molding, sheet molding, blow molding, injection molding, extrusion molding, etc. Examples of film molding include extrusion lamination molding, T-die film molding, and inflation molding (air cooling, water cooling, multi-stage cooling, high-speed processing). The obtained film can be used as a single layer, but by making it multilayer, various functions can be further imparted. Examples of molding methods used in this case include co-extrusion. On the other hand, by a lamination molding method such as extrusion lamination molding or dry lamination method, it is possible to laminate with paper or barrier film (aluminum foil, vapor deposition film, coating film, etc.) that is difficult to co-extrude. In short, in obtaining a multilayer film in which at least one surface layer is formed from a layer made of the ethylene-based resin composition (Z), such methods can be used as a means for laminating a layer made of the ethylene-based resin composition (Z) on a substrate.

[0194] It is possible to create high-performance products by multi-layering using blow molding, injection molding, extrusion molding, and co-extrusion methods, just like film molding. Examples of molded articles obtained by processing the ethylene-based resin composition (Z) of the present invention include films, sheets, blown infusion bags, blown bottles, gasoline tanks, tubes by extrusion molding, pipes, electric wire coverings, tear-off caps, injection molded articles such as daily necessities, fibers, and large molded articles by rotational molding.

[0195] Furthermore, the films obtained by processing the ethylene-based resin composition (Z) of the present invention are suitable for various packaging films such as liquid packaging bags, liquid soup bags, liquid paper containers, laminated raw material, special-shaped liquid packaging bags (standing pouches, etc.), standard bags, heavy-duty bags, wrap films, sugar bags, oily packaging bags, food packaging, etc., protective films, infusion bags, agricultural materials, bag-in-boxes, semiconductor materials, medicines, clean films used for packaging foods, etc. In this case, it can be used as a film having one or more layers made of the ethylene-based resin composition (Z), or as a multilayer film having a form in which a layer made of the ethylene-based resin composition (Z) is laminated on a substrate made of nylon, polyester, polyolefin film, etc. The raw material for the substrate of the multilayer film may contain an ethylene-based polymer or a propylene-based polymer containing a biomass-derived monomer. EXAMPLES

[0196] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the description of the following examples.

[0197] [Measurement or evaluation method] In the following examples, various physical properties of ethylene-α-olefin copolymers and the like were measured by the methods described in [Mode for Carrying Out the Invention], and the following methods were used as evaluation methods not described in [Mode for Carrying Out the Invention].

[0198] Inflation molding evaluation : A film having a thickness of 40 μm was obtained from the ethylene polymer using an inflation molding machine having a 50 mmφ extruder and a die diameter of 100 mm manufactured by Sumitomo Heavy Industries Modern Co., Ltd. under the conditions of a die temperature of 190° C., an extrusion rate of 29 kg / hr, and a tube width of 320 mm. The following items were measured for the obtained film.

[0199] [Hayes] The total haze of the obtained film was measured in accordance with JIS 7136.

[0200] [Internal Haze] The obtained film was placed in a cell filled with cyclohexanol, and the film was measured according to JIS 7136.

[0201] [Gloss 20°] The gloss of the film obtained was measured at an incident angle of 20° in accordance with JIS Z8741.

[0202] [Tensile modulus] The obtained film was measured in the MD and TD directions in accordance with JIS K6781 at a test speed of 200 mm / min.

[0203] [Dirt Impact] In accordance with ASTM D1709 A method, the obtained film was clamped with an air clamp method, a hemispherical dart was dropped from a certain height, and the load at which the film was broken by 50% was read from the graph.

[0204] [Blocking force] A test piece consisting of two of the obtained tubular films stacked with their inner surfaces facing each other was aged for three days under a load of 10 kg at 50° C. After that, the test piece was cut into a width of 200 mm, and the force required to separate the test pieces at 23° C. and 200 mm / min was measured as the blocking force.

[0205] [Melt tension of composition] The obtained film was measured using a capillary rheometer: Capillograph 1D manufactured by Toyo Seiki Seisakusho, Ltd. The conditions were: resin temperature 190°C, melting time 6 minutes, barrel diameter 9.55 mmφ, extrusion speed 15 mm / min, winding speed 24 m / min (if the molten filament breaks, the winding speed is reduced by 5 m / min), nozzle diameter 2.095 mmφ, nozzle length 8 mm.

[0206] [Resin pressure] The resin pressure during film molding under the above conditions was recorded.

[0207] [Melted film stability] The stability of the molten film (bubble) during film molding was visually confirmed under the above conditions. The symbols (evaluation results) in Table 12 have the following meanings. 〇: The molten film (bubble) is stable and there is little shaking. △: The stability of the molten film (bubble) is somewhat poor and shaking is observed. ×: The molten film (bubble) is unstable and shakes violently.

[0208] [Raw materials used] The transition metal compounds and component (G) used in the examples are as follows. Transition metal compound (A-1): dimethylsilylene(2-indenyl)(4-(3,5-di-tert-butyl-4-methoxyphenyl)-7-methoxy-1-indenyl)zirconium dichloride [synthesized by the method described in JP 2019-059933 A.] Transition metal compound (B-1): dimethylsilylene(3-n-propylcyclopentadienyl)(cyclopentadienyl)zirconium dichloride [synthesized based on the method described in Japanese Patent No. 5455354.] Transition metal compound (B-2): isopropylidene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconium dichloride [synthesized based on the method described in JP-A-4-69394.] Ingredient (G-1): Lauryldiethanolamine (Kao Corporation) Ingredient (G-2): Emulgen (registered trademark) 108 (manufactured by Kao Corporation)

[0209] <Synthesis of prepolymerization catalyst (XP-1)> In a 270 L reactor equipped with a stirrer, silica (average particle size 70 μm, specific surface area 340 m) manufactured by Fuji Silysia Ltd. was placed as a solid carrier (S) under a nitrogen atmosphere. 2 / g, pore volume 1.3cm 310 kg of methylaluminoxane (1.0 g, calcined at 250°C) was suspended in 77 L of toluene and then cooled to 0-5°C. 20.4 L of toluene solution of methylaluminoxane (3.5 mol / L in terms of Al atom) was added dropwise to this suspension over 30 minutes as component (C). At this time, the temperature in the system was kept at 0-5°C. After reacting for 30 minutes at 0-5°C, the temperature was raised to 95-100°C over about 1.5 hours, and the reaction was continued for 4 hours at 95-100°C. The temperature was then lowered to room temperature, the supernatant liquid was removed by decantation, and the mixture was washed twice with toluene, and a total of 58.0 L of toluene slurry was prepared. A part of the obtained slurry component was collected and the concentration was examined, and the slurry concentration was 248.0 g / L and Al concentration was 1.21 mol / L.

[0210] Next, 6.1 L of the toluene slurry obtained above and 21.9 L of toluene were charged into a reactor equipped with a stirrer and had an internal volume of 114 L, which had been thoroughly purged with nitrogen, and 5.4 L of an 8 mM toluene solution of a transition metal compound (A-1) was added. After contacting for 1 hour at a system temperature of 20 to 25 ° C., the supernatant was removed by decantation, and the mixture was washed twice with hexane to prepare a total slurry of 30.9 L. While adjusting the obtained slurry to 10 to 15 ° C., 3.1 L of a 0.92 M hexane solution of diisobutylaluminum hydride was added, and ethylene gas was started to be supplied at a flow rate of 0.74 kg / hr. After adding 34.3 mL of 1-hexene, the temperature was raised, and 34.3 mL of 1-hexene was added 5 times in total every hour while adjusting the system temperature to 32 to 38 ° C., and when the ethylene supply amount reached 4.5 kg 6 hours after the start of ethylene supply, the ethylene supply was stopped. The system was then thoroughly replaced with nitrogen, the supernatant was removed by decantation, and the mixture was washed four times with hexane to prepare a slurry of 21.9 L in total. While maintaining the obtained slurry at 35-40°C, 6.1 L of a 10 g / L hexane solution of component (G-1) was added and contacted for 2 hours. The obtained slurry was entirely inserted into an evaporative dryer with a 43 L internal volume and equipped with a stirrer under nitrogen atmosphere, and the inside of the dryer was depressurized to -68 kPaG over about 60 minutes, and when the pressure reached -68 kPaG, the mixture was vacuum dried for about 4.3 hours to remove hexane and volatile matters in the prepolymerized catalyst component. The pressure was further reduced to -100 kPaG, and when the pressure reached -100 kPaG, the mixture was vacuum dried for 8 hours to obtain 6.2 kg of prepolymerized catalyst (XP-1). A portion of the obtained prepolymerized catalyst (XP-1) was sampled and the composition was examined, and it was found that 0.56 mg of Zr atoms were contained per 1 g of the prepolymerized catalyst component.

[0211] <Synthesis of prepolymerization catalyst (XP-2)> According to the method for producing the prepolymerized catalyst component (XP-1) described in Japanese Patent No. 5943941, 6.1 kg of a prepolymerized catalyst (XP-2) was obtained.

[0212] <Production of ethylene polymer> [Production Example 1] (Production of ethylene-α-olefin copolymer (A-1)) An ethylene-based polymer was produced by a gas phase polymerization process using a fluidized bed type gas phase polymerization reactor. 24 kg of spherical ethylene polymer particles having an average particle size of 900 μm were introduced into the reactor in advance, and nitrogen was supplied to form a fluidized bed. Then, ethylene, hydrogen, 1-hexene, a prepolymerization catalyst, and Electrostripper (registered trademark) EA were continuously supplied so as to reach a steady state under the polymerization conditions shown in Table 1. The polymerization reaction product was continuously extracted from the reactor and dried in a drying device to obtain a powder of ethylene-α-olefin copolymer (A-1).

[0213] [Manufacturing Examples 2-6, 9-10] (Production of Ethylene-α-Olefin Copolymers (A-2) to (A-6), (A-9), and (A-10)) Powders of ethylene-α-olefin copolymers (A-2) to (A-6), (A-9), and (A-10) were obtained in the same manner as in Production Example 1, except that the polymerization conditions were changed as shown in Table 8. Note that Table 8 lists Chemistat (registered trademark) 2500 (manufactured by Sanyo Chemical Industries, Ltd.) as a component that was not used in Production Example 1.

[0214] [Production Example 7] (Production of ethylene-α-olefin copolymer (a-7)) Using the prepolymerization catalyst component (XP-2), a powder of an ethylene-α-olefin copolymer (a-7) was obtained according to the method for producing an ethylene polymer (α-1) described in Japanese Patent No. 5,943,941.

[0215] <Measurement of polymer properties> [Ethylene-α-olefin copolymer (A-1)] The powder of ethylene-α-olefin copolymer (A-1) obtained in Production Example 1 was added with 850 ppm of Sumilizer GP (manufactured by Sumitomo Chemical Co., Ltd.) and 210 ppm of calcium stearate (manufactured by Nitto Kasei Kogyo Co., Ltd.) as heat stabilizers, and then melt-kneaded using a twin-screw 46 mmφ extruder manufactured by Ikegai Co., Ltd. at a set temperature of 200 ° C. and a screw rotation speed of 300 rpm, and then extruded into a strand shape and cut to obtain pellets. The obtained pellets were used as measurement samples and physical properties were measured. The measurement results are shown in Table 9.

[0216] [Ethylene-α-olefin copolymers (A-2) to (a-7), (A-9), (A-10)] Pellets were prepared and their properties were measured in the same manner as in the measurement of the physical properties of the ethylene-α-olefin copolymer (A-1), except that the ethylene-α-olefin copolymer (A-1) was replaced with any of the ethylene-α-olefin copolymers (A-2) to (a-7), (A-9), and (A-10) obtained in Production Examples 2 to 7. The measurement results are shown in Table 9.

[0217] [Ethylene-based polymer (a-8)] Suntec-LD M2504 (density: 927 kg / m), a high-pressure low-density polyethylene manufactured by Asahi Kasei Corporation 3 The physical properties of the ethylene-α-olefin copolymer (A-1) of Production Example 1 were measured in the same manner as for the ethylene-α-olefin copolymer (A-1) of Production Example 1. The measurement results are shown in Table 9.

[0218] [Ethylene-α-olefin copolymer (B-1)] The physical properties of Evolu SP1510 manufactured by Prime Polymer Co., Ltd. were measured in the same manner as for the ethylene-α-olefin copolymer (A-1) in Production Example 1. The measurement results are shown in Table 10.

[0219] [Ethylene-α-olefin copolymer (B-2)] Evolu SP2120 manufactured by Prime Polymer Co., Ltd. was subjected to physical property measurements in the same manner as for the ethylene-α-olefin copolymer (A-1) in Production Example 1. The measurement results are shown in Table 10.

[0220] [Ethylene-α-olefin copolymer (B-3)] The physical properties of Evolu SP1520 manufactured by Prime Polymer Co., Ltd. were measured in the same manner as for the ethylene-α-olefin copolymer (A-1) in Production Example 1. The measurement results are shown in Table 10.

[0221] [Ethylene-α-olefin copolymer (B-4)] The physical properties of Evolu SP1540 manufactured by Prime Polymer Co., Ltd. were measured in the same manner as for the ethylene-α-olefin copolymer (A-1) in Production Example 1. The measurement results are shown in Table 10.

[0222] <Production of ethylene-based resin composition> [Example 1] 20% by weight of the pellets of the ethylene-α-olefin copolymer (A-1) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-1) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 11.

[0223] [Example 2] 20% by weight of the pellets of the ethylene-α-olefin copolymer (A-1) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-2) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 11.

[0224] [Example 3] 20% by weight of the pellets of the ethylene-α-olefin copolymer (A-2) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-2) were dry-blended and subjected to inflation molding evaluation. The evaluation results are shown in Table 11.

[0225] [Example 4] 20% by weight of the pellets of the ethylene-α-olefin copolymer (A-3) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-1) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 11.

[0226] [Example 5] 20% by weight of the pellets of the obtained ethylene-α-olefin copolymer (A-3) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-2) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 11.

[0227] [Example 6] 20% by weight of the pellets of the ethylene-α-olefin copolymer (A-4) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-1) were dry blended and subjected to inflation molding evaluation. The evaluation results are shown in Table 11.

[0228] [Example 7] 20% by weight of the pellets of the ethylene-α-olefin copolymer (A-4) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-2) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 11.

[0229] [Example 8] 20% by weight of the pellets of the ethylene-α-olefin copolymer (A-5) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-1) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 11.

[0230] [Example 9] 20% by weight of the pellets of the obtained ethylene-α-olefin copolymer (A-5) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-2) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 11.

[0231] [Example 10] 20% by weight of the pellets of the obtained ethylene-α-olefin copolymer (A-6) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-1) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 11.

[0232] [Example 11] 40% by weight of the pellets of the ethylene-α-olefin copolymer (A-2) and 60% by weight of the pellets of the ethylene-α-olefin copolymer (B-3) were dry-blended and subjected to inflation molding evaluation. The evaluation results are shown in Table 11.

[0233] [Example 12] The pellets of the ethylene-α-olefin copolymer (A-3) (8% by weight) and the pellets of the ethylene-α-olefin copolymer (B-1) (92% by weight) were dry-blended and subjected to inflation molding evaluation. The evaluation results are shown in Table 11.

[0234] [Example 13] The pellets of the ethylene-α-olefin copolymer (A-9) were dry-blended with 75% by weight of the pellets of the ethylene-α-olefin copolymer (B-1) at 25% by weight, and the pellets were subjected to inflation molding evaluation. The evaluation results are shown in Table 12.

[0235] [Example 14] The pellets of the ethylene-α-olefin copolymer (A-9) were dry-blended with 75% by weight of the pellets of the ethylene-α-olefin copolymer (B-4) at 25% by weight, and the pellets were subjected to inflation molding evaluation. The evaluation results are shown in Table 12.

[0236] [Example 15] The pellets of the ethylene-α-olefin copolymer (A-10) were dry-blended with 60% by weight of the pellets of the ethylene-α-olefin copolymer (B-4) at 40% by weight, and the pellets were subjected to inflation molding evaluation. The evaluation results are shown in Table 12.

[0237] [Example 16] 90% by weight of the pellets of the obtained ethylene-α-olefin copolymer (A-10) and 10% by weight of the pellets of the ethylene-α-olefin copolymer (B-1) were dry blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 12.

[0238] [Comparative Example 1] 40% by weight of the pellets of the obtained ethylene-α-olefin copolymer (a-7) and 60% by weight of the pellets of the ethylene-α-olefin copolymer (B-1) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 11.

[0239] [Comparative Example 2] 20% by weight of the pellets of the obtained ethylene-α-olefin copolymer (a-7) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-1) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 11.

[0240] [Comparative Example 3] The pellets of the ethylene-α-olefin copolymer (a-7) (80% by weight) and the pellets of the ethylene-α-olefin copolymer (B-1) (20% by weight) were dry-blended, and the blown film extrusion evaluation was performed. The evaluation results are shown in Table 11.

[0241] [Comparative Example 4] 20% by weight of the pellets of the ethylene polymer (a-8) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-1) were dry blended and subjected to inflation molding evaluation. The evaluation results are shown in Table 11. The melt tension of the composition could not be measured because the molten resin broke during stretching.

[0242] [Comparative Example 5] 20% by weight of the pellets of the ethylene polymer (a-8) and 80% by weight of the pellets of the ethylene-α-olefin copolymer (B-2) were dry blended and subjected to inflation molding evaluation. The evaluation results are shown in Table 11.

[0243] [Comparative Example 6] The pellets of the ethylene-α-olefin copolymer (a-7) (80% by weight) and the pellets of the ethylene-α-olefin copolymer (B-1) (20% by weight) were dry-blended, and the inflation molding evaluation was performed. The evaluation results are shown in Table 12.

[0244] [Comparative Example 7] An inflation molding evaluation was carried out using ethylene-α-olefin copolymer (B-4). The melt film stability was poor, and stable film production was not possible.

[0245] [Comparative Example 8] An inflation molding evaluation was carried out using the ethylene-α-olefin copolymer (B-1). The evaluation results are shown in Table 12. The resin pressure during molding was high, and the bubble stability was somewhat poor, resulting in some shaking.

[0246] [Table 8]

[0247] [Table 9]

[0248] [Table 10]

[0249] [Table 11]

[0250] [Table 12]

[0251] As is clear from Table 11, the examples have superior film transparency compared to Comparative Examples 1 to 3, superior blocking resistance compared to Comparative Example 4, and superior mechanical strength (dart impact) compared to Comparative Example 5.

Claims

1. An ethylene-α-olefin copolymer (A) which is a copolymer of ethylene and an α-olefin having 4 to 10 carbon atoms and satisfies the following requirements (1) to (4) and (9); and (B) an ethylene-α-olefin copolymer which is a copolymer of ethylene and an α-olefin having 4 to 10 carbon atoms and satisfies the following requirements (a) to (c): Ethylene-based resin composition (Z). (1) Density is 890 kg / m 3 More than 935kg / m 3 It is in the following range: (2) The melt flow rate (MFR) at 190° C. under a load of 2.16 kg is in the range of 0.1 g / 10 min or more and less than 3.0 g / 10 min. (3) Melt tension [MT (g)] at 190°C and shear viscosity [η * (P)] ratio [MT / η * (g / P)] is 1.20×10 -4 Above 2.90 x 10 -4 It is in the following range: (4) Zero shear viscosity at 200 ° C [η 0 (P)] and the weight average molecular weight (Mw) measured by a GPC-viscosity detector method (GPC-VISCO) satisfy the following relational expression (Eq-1). 0.01×10 -13 ×Mw 3.4 ≦ η 0 ≦ 3.5×10 -13 ×Mw 3.4 ・・・(Eq-1) (9) The melting curve obtained by differential scanning calorimetry (DSC) has multiple peaks. (a) Density is 890 kg / m 3 More than 930kg / m 3 It is in the following range: (b) The melt flow rate (MFR) at 190° C. under a load of 2.16 kg is in the range of 0.1 g / 10 min or more and 10 g / 10 min or less. (c) The intrinsic viscosity [[η] (dl / g)] measured in decalin at 135° C. and the weight average molecular weight (Mw) measured by a GPC-viscosity detector method (GPC-VISCO) satisfy the following relational formula (Eq-4). 1.90×10 -4 ×Mw 0.776 ≦[η]≦ 2.80×10 -4 ×Mw 0.776 ・・・(Eq-4)

2. The mass fraction (W A ) is 1 mass% or more and 50 mass% or less, and the mass fraction (W B ) is 50% by mass or more and 99% by mass or less (provided that W A And W B The total of is 100% by mass.) The ethylene-based resin composition (Z) according to claim 1.

3. The mass fraction (W A ) is more than 50 mass% and not more than 99 mass%, and the mass fraction (W B ) is 1 mass % or more and less than 50 mass % (provided that W A And W B The total of is 100% by mass.) The ethylene-based resin composition (Z) according to claim 1.

4. The ethylene-α-olefin copolymer (A) satisfies the following requirement (5): (5) The number average molecular weight (Mn), weight average molecular weight (Mw) and Z average molecular weight (Mz) measured by a GPC-viscosity detector method (GPC-VISCO) satisfy the following relational formula (Eq-2). -7.0 ≦ Mz / Mw - Mw / Mn ≦ 2.0 ... (Eq-2)

5. The ethylene-based resin composition (Z) according to any one of claims 1 to 4, wherein the ethylene-α-olefin copolymer (A) further satisfies the following requirement (6): (6) The ratio Mz / Mw of the Z-average molecular weight (Mz) to the weight-average molecular weight (Mw) measured by a GPC-viscosity detector method (GPC-VISCO) is in the range of 4.0 or more and 15.0 or less.

6. The ethylene-based resin composition (Z) according to any one of claims 1 to 5, wherein the ethylene-α-olefin copolymer (A) further satisfies the following requirement (7): (7) The intrinsic viscosity [[η] (dl / g)] measured in decalin at 135° C. and the weight average molecular weight (Mw) measured by a GPC-viscosity detector method (GPC-VISCO) satisfy the following relational formula (Eq-3). 0.7×10 -4 ×Mw 0.776 ≦[η]≦ 1.65×10 -4 ×Mw 0.776 ・・・(Eq-3)

7. The ethylene-α-olefin copolymer (A) satisfies the following requirement (8): (8) 1 The total amount of vinyl, vinylidene, di-substituted internal olefin, and tri-substituted internal olefin per 1000 carbon atoms (units / 1000C) measured by H-NMR is in the range of 0.1 to 1.

0.

8. The ethylene-based resin composition (Z) according to any one of claims 1 to 7, further comprising a thermoplastic resin (excluding the ethylene-α-olefin copolymer (A) and the ethylene-α-olefin copolymer (B)).

9. A molded article comprising the ethylene-based resin composition (Z) according to any one of claims 1 to 8.

10. A film comprising the ethylene-based resin composition (Z) according to any one of claims 1 to 8.

11. A multilayer film comprising a layer made of the ethylene-based resin composition (Z) according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Ethylenic copolymer and production thereof

    JP1990276807A

  • Ethylene copolymer

    JP1992213309A

  • Laminating resin composition

    JP1995026079A

  • Ethylene polymer with heightened process-ability

    JP1996311260A

  • Ethylene polymer and molding obtained therefrom

    JP2006233207A